Geomorphological dynamics at the coast: A sedimentary stratigraphy for Atlit-Yam, the earliest coastal village at the Eastern Mediterranean and its submerged landscape - Vishal Kataria; Gilad Shtienberg; Isaac Ogloblin Ramirez; Roni Zuckerman-Cooper; Nimer Taha; Elle Grono; Marko Runjajić; Ehud Galili; Nicolas Waldmann; David E. Friesem (Quaternary International, 2026)

Ecotoxicological profile of a high prevalence marine disease area in Florida's Gulf coast - Manes Costanza; Herren Richard; Kozuch Marianne; Cooper Evan; Lilyestrom Margaret; Evans Daniel; Godfrey David; Duffy David; Capua Ilaria; Carthy Raymond (Marine Pollution Bulletin, 2026)

Oil spills in inland freshwaters: A review of recent incidents, mitigation practices, and ecological impacts in the United States - Joshua O. Olowoyo; Nan Zou; David Cooper; Kurt Hansen; Vince Palace; Kenneth Lee; Qin Xin; Amarjeet Bassi; Ying Zheng (Science of The Total Environment, 2026)

Prevalence of foodborne pathogens and indicator microorganisms on Arizona and California grown commercial cantaloupe melons and in environmental samples - Richard Park; David Rowlands; Libin Zhu; Victoria Obergh; Martin Porchas; Paul Brierley; Kevin Crosby; Mendel Friedman; Tom Turini; Bhimanagouda Patil; Kerry K. Cooper; Sadhana Ravishankar (Food Microbiology, 2026)

Microfocus X-ray computed tomography to evaluate ostracode shell density and other metrics for monitoring ocean acidification in the Arctic Ocean - Laura Gemery; Katsunori Kimoto; David J. Horne; Michiyo Yamamoto-Kawai; Siyi Yin; Ryan McAleer; Lee W. Cooper; Jacqueline M. Grebmeier; Aaron M. Jubb; Masanobu Yamamoto (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Biallelic germline MBD4 mutations predispose to colorectal polyposis, hypermutated AML, and schwannomas - Julia Cooper; Brittany L. Stewart; Lauren Bokovitz; Hetty Carraway; Sudipto Mukherjee; David Liska; Sumithira Vasu; Harry Lesmana; James S. Blachly (Familial Cancer, 2026)
Biallelic pathogenic variants in the MBD4 gene have recently been associated with an autosomal recessive cancer predisposition syndrome deemed “ MBD4 -associated neoplasia syndrome (MANS)”. Early reports of individuals with MANS highlight the propensity to develop young onset colorectal polyposis and hyper-mutated acute myeloid leukemia (AML). In the following case series, we present four patients with MANS from three families with polyps and AML, as well as additional features previously less described, such as schwannoma and thyroid cancer. This series increases the total number of reported cases by 27%, with the intention of achieving a more robust understanding of the full phenotypic spectrum of MANS.

Evolving glacier landsystems during Patagonian Ice Sheet recession influenced by a changing topographic setting - Emma-Louise Cooper; Bethan J. Davies; Varyl.R. Thorndycraft; Adrian P. Palmer; Juan-Luis García; David J.A. Evans; Christopher Lüthgens; Andrew N. Mackintosh (Geomorphology, 2026)

Multi-gene phylogeny and morphology of Pleurotus in Aotearoa New Zealand reveal a new variety of Pleurotus pulmonarius - David Hera; Jerry Cooper; Peter K. Buchanan; Manpreet K. Dhami; Ian A. Dickie (Fungal Biology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Decoupled Climatic Drivers of Tree and Ground‐Layer Carbon Uptake in Mountain Ecosystems Around the World - Max Mallen‐Cooper; Maja K. Sundqvist; David A. Wardle; Radim Šarlej; Rose E. Brinkhoff; Aimée T. Classen; Eliška Kuťáková; Daniel B. Metcalfe; M. Noelia Barrios‐Garcia; Julie R. Deslippe; Kobayashi Makoto; Jane Mallen‐Cooper; et al. (Global Change Biology, 2026)
One of the key ecological processes affected by climate change is plant carbon uptake. However, there is substantial uncertainty about how plant carbon uptake will respond to warming in mountain ecosystems, which are known for sharp temperature gradients and abrupt shifts in vegetation structure. Specifically, we lack an understanding of whether these response trajectories over time will be linear or non‐linear, and how they might vary among mountain ecosystems globally. Here, we measured ecosystem Gross Primary Productivity (GPP) along forest‐tundra elevational gradients in the mountain regions of five countries (Argentina, Australia, France, Sweden, USA) to infer future trajectories of carbon uptake, and whether any non‐linear changes might occur. We also examined the role of microclimate in driving GPP responses. We found that whole‐ecosystem GPP increased with increasing macroclimatic temperature (decreasing elevation), but this response was dominated by a sharp non‐linear increase at the transition from tundra to forest (i.e., the treeline). In contrast, ground‐layer GPP was largely independent of macroclimate, but often responded strongly, and linearly, to microclimate (growing degree days > 5°C, mean growing season temperature). This pattern reflected a frequent decoupling of microclimate from the expected temperature‐elevation relationship, likely driven by such processes as cold‐air drainage, limited near‐surface air mixing, and shading by trees. The contrasting responses of GPP among global temperature gradients indicates strong context dependence at both local and continental scales, although in a few cases, biomass and leaf nitrogen were important moderators. These findings suggest that future shifts in carbon uptake in mountains will be mainly controlled by tree range expansion. Our results highlight the need to consider species responses on different spatial scales, and to increase representation of undersampled regions to capture the full breadth of ecological responses to climate change.

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Plant and Soil Function Increase With Larger and Older Coarse Woody Debris - Max Mallen‐Cooper; Millie Vernon; David J. Eldridge (Global Ecology and Biogeography, 2026)
Aim Coarse woody debris is increasingly being used in ecological restoration. We aimed to assess the global impacts of woody debris on ecosystem properties and functions. Location Global. Major Taxa Studied Soil biota, plants, soil function. Methods We conducted a quantitative global meta‐analysis of 66 studies (5234 observations) to assess how woody debris influences ecosystem health and specific ecological components, focusing on soil properties, soil biota, and plants. Results Woody debris significantly enhanced soil function, biodiversity, and the abundance of biota. The positive impact on diversity and abundance increased with debris size, and in the case of abundance, age of debris. Most individual attributes such as soil carbon, soil nitrogen, soil infiltration, and the abundance and diversity of microbes, invertebrates, and plants, were enhanced by the addition of woody debris, and generally to a greater extent when the debris was larger and older. Main Conclusions Our results suggest that larger and older pieces of woody debris are more likely to promote ecological functioning and biodiversity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Two Contrasting Demographic Processes Shape the Divergence and Evolution of the Widespread Arid Zone Specialist, Petrogale lateralis - Sally Potter; Craig Moritz; Kym Ottewell; Emily Roycroft; Anna J. MacDonald; Margaret Byrne; Steven J. B. Cooper; David J. Pearson; Mark D. B. Eldridge (Molecular Ecology, 2026)
Organisms living in arid environments are predicted to be at increased risk of extinction under climatic and anthropogenic change. Response to past climate change can provide some insights into these risks; however, our understanding of the diversification and evolutionary history of many arid‐adapted species is still limited, particularly in Australia. Here, we evaluate the demographic and evolutionary history of a widespread Australian marsupial, the black‐footed rock‐wallaby ( Petrogale lateralis ), with a highly fragmented contemporary distribution across Australia's arid biome and offshore islands. Combining genomic data from historical and modern samples, we evaluate the divergence history of the five P. lateralis subspecies. Our results show that the species has experienced a Pleistocene‐age demographic expansion across the Australian arid biome, with subsequent geographic fragmentation of populations and subspecies. We find negligible gene flow between most extant populations/subspecies, yet low divergence between populations of P. l. lateralis and currently recognised subspecies. Individuals on islands have extremely low genetic diversity and high inbreeding coefficients, in contrast to naturally fragmented mainland populations, suggesting a stronger bottleneck experienced on islands. Our results indicate connectivity of populations within the past ~160–640 kya despite their current disjunct distributions, providing important context for conservation management and potential genetic rescue. However, given the large ecological gradient and chromosomal variation within this species, assessment of ecological differences and risks of outbreeding depression will be important before decisions to mix across geographically distant populations and/or subspecies. This study demonstrates how museum genomics improves our ability to resolve complex evolutionary histories and guide conservation.

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

The impact of climate change on the flux and fate of metals in freshwater systems: Implications for metal exposure across different scales - Farhan R. Khan; Nicolas R. Bury; Christopher A. Cooper; David Boyle; Elizabeth Middleton; Simon D. Herzog (Environmental Research, 2025)

Late Quaternary inundation and desiccation of Megalake Chad traced in dust records from the Equatorial Atlantic Ocean - Anya J. Crocker; Christopher W. Kinsley; Amy M. Jewell; Paul S. Breeze; Nicholas A. Drake; David McGee; Charles S. Bristow; Katie Manning; Claudia Di Biagio; Paola Formenti; William R.C. Burton; Annie L. Murray; et al. (Quaternary Science Reviews, 2025)

Rapid riparian ecosystem decline in Rocky Mountain National Park - David J. Cooper; E. William Schweiger; Jeremy R. Shaw; Cherie J. Westbrook; Kristen Kaczynski; Hanem Abouelezz; Scott M. Esser; Koren Nydick; Isabel de Silva; Rodney A. Chimner (Conservation Biology, 2025)
Understanding the drivers of ecosystem collapse is critical for resource management, particularly for protected areas mandated to preserve biodiversity. In Rocky Mountain National Park, Colorado, tall willows ( Salix spp.) dominated riparian vegetation, and a beaver–willow state was the natural ecosystem type in the Colorado River headwaters. However, willows comprise a portion of elk diets and are a preferred food for recently introduced moose, and the vegetation structure has changed dramatically since the early 2000s. To assess ecosystem changes, we analyzed time‐series data on willow height from 1997 to 2021 inside and outside 3 exclosures built to exclude ungulates, area of tall willows in 1999 and 2019, area of open water from 1953 to 2019, vegetation composition in 1998 and 2021, groundwater depth from 1996 to 2021, surface water flow from 1953 to 2023, and climate from 1950 to 2023. Tall willow coverage and open water area declined by >90% from 1999 to 2019. Willow height outside the ungulate exclosures declined by more than 75% since the 1990s; yet, within exclosures that were formerly browsed, willow height increased by up to 500%. Tall willow communities have largely been replaced by grasslands. Browsing by elk and moose likely played a pivotal role in triggering a collapse of the beaver–willow state and the formation of an alternative moose–elk–grassland state that appears stable and may be difficult to reverse without direct human action. Restoration efforts will depend on a reduction in herbivory and reconnection of the river with its floodplain.

SMARCB1-related schwannomatosis and other SMARCB1-associated phenotypes: clinical spectrum and molecular pathogenesis - Hildegard Kehrer-Sawatzki; David N. Cooper (Familial Cancer, 2025)
SMARCB1 is a core unit of the BAF chromatin remodelling complex and its functional impairment interferes with the self-renewal and pluripotency of stem cells, lineage commitment, cellular identity and differentiation. SMARCB1 is also an important tumour suppressor gene and somatic SMARCB1 pathogenic variants (PVs) have been detected in ~ 5% of all human cancers. Additionally, germline SMARCB1 PVs have been identified in patients with conditions as clinically diverse as Rhabdoid Tumour Predisposition Syndrome type 1 (RTPS1), schwannomatosis and neurodevelopmental disorders such as Coffin-Siris syndrome (CSS). RTPS1 is characterized by the occurrence of highly malignant atypical teratoid rhabdoid tumours (AT/RT) affecting mostly infants, whereas SMARCB1 -related schwannomatosis is generally diagnosed after the age of 30 and is characterized by benign schwannomas. Patients with germline SMARCB1 PVs and neurodevelopmental disorders do not usually develop SMARCB1 -deficient tumours but instead exhibit severe intellectual disability and congenital malformations. It is intriguing how germline SMARCB1 PVs can be responsible for these very different pathologies. However, a network of different factors has emerged that play important roles in this context. Thus, the tumour phenotype associated with germline SMARCB1 PVs is determined by the nature and location of the SMARCB1 mutation and the timing of SMARCB1 inactivation in specific progenitor cells. Biallelic complete loss of SMARCB1 function during a narrow time window of early embryonic development in neural crest cells is essential for AT/RT development. By contrast, hypomorphic SMARCB1 PVs during later developmental stages affecting more differentiated Schwann cell precursors give rise to schwannomas. However, the loss of the wild-type SMARCB1 allele is insufficient for schwannoma growth which appears to be dependent upon concomitant somatic NF2 PVs in patients with SMARCB1 -related schwannomatosis according to the four-hit/three-step model of tumorigenesis. In patients with neurodevelopmental disorders such as CSS, germline PVs would appear to cluster within the C-terminal SMARCB1 domain, interfering with the nucleosomal interactions of SMARCB1 but not with its tumour suppressor activity.

Microvertebrates from a Rhaetian neptunian dyke at Holwell, Somerset: Dating the fissures - Oliver J. Weeks; Rebecca B. Cooper; David I. Whiteside; Christopher J. Duffin; Charles Copp; Claudia Hildebrandt; Deborah Hutchinson; Michael J. Benton (Proceedings of the Geologists' Association, 2025)

The effectiveness of connectivity of existing biodiversity corridors in Central Annamite, Vietnam - Van Tri Tin Nguyen; David Newell; Les Christidis; Cooper Schouten; Cody Aylward (Journal for Nature Conservation, 2025)

Coexistence, Extinction and Survival—The Evolutionary History of Bison Species in Western Eurasia - Bastien Llamas; Ayla L. van Loenen; Kieren J. Mitchell; Emilia Hofman‐Kamińska; Hervé Bocherens; Holly Heiniger; Martina Pacher; Daniel Makowiecki; Giedrė Piličiauskienė; Dorothée G. Drucker; David Brown; Zoe A. Thomas; et al. (Global Change Biology, 2025)
European bison ( Bison bonasus ) are one of the few European megafaunal species to survive the Late Pleistocene mass megafaunal extinction. Current conservation management efforts have proceeded in the absence of information about their evolutionary history, which has been obscured by recent severe population bottlenecks. We characterized mitochondrial genomes from 135 ancient bison samples spanning > 50,000 years (> 50 ka) across the Eurasian continent and detected three distinct phylogenetic groups: two distinct clades of European bison and the extinct steppe bison ( Bison priscus ). The geographical distributions and dietary/ecological signatures of the three groups overlapped during the Late Pleistocene climate cycles and tracked environmental changes including vegetation cover and human impacts. The abundance of European bison specimens responded negatively to the extent of forest cover, including Holocene cycles of abrupt atmospheric‐ocean circulation changes originating in the North Atlantic. European bison remain preferentially adapted to an open environment, but with today's anthropogenic landscapes, are now largely restricted to forest habitats with negative implications under scenarios of future environmental change.

Integrating gene mutation spectra from tumors and the general population with gene expression topological networks to identify novel cancer driver genes - Shuangyu Yang; Dan He; Ling Li; Zhiya Lu; Shaoying Li; Tianjun Lan; Feiyi Liu; Huasong Zhang; David N. Cooper; Huiying Zhao (Human Genetics, 2025)

Skull roof anatomy of the Early Jurassic (Toarcian) acipenseriform †Gyrosteus mirabilis Woodward ex Agassiz, from Yorkshire, England, elucidates diversity of †Chondrosteidae - Samuel L.A. Cooper; Megan Jacobs; Lucrezia Ferrari; David M. Martill (Proceedings of the Geologists' Association, 2025)

Hydrogeochemical and Vegetation Characterization of Sphagnum-dominated Peatlands in the Puget Lowlands of Washington State, USA - F. Joseph Rocchio; Tynan Ramm-Granberg; Jeremy R. Shaw; David J. Cooper (Wetlands, 2025)
Sphagnum -dominated peatlands in the Puget lowlands of western Washington provide important biodiversity, ecological functions, and cultural resources. Historical and ongoing land uses have resulted in regional loss and degradation of these ecosystems. Effective conservation and management of peatland biodiversity and other ecological values requires an understanding of a peatland’s landscape setting, hydrological processes, water chemistry, biotic patterns, and response to human stressors. This research identified the climate, watershed size, hydrologic regime, and land use characteristics influencing these peatlands. Shallow groundwater, vertical and lateral water movement, pore water chemistry, and vegetation composition were measured in two locations within each of the 17 study sites: the peatland center and lagg. Study sites had some ecological characteristics similar to ombrotrophic bogs in the Northern Hemisphere, but many sites lacked strong hydrological evidence of being solely rain-fed. Climate, watershed size, and adjacent land use were correlated with hydrological, chemical, and vegetation variability across study sites. Land use correlations with ecological changes were most prominent in laggs but some effects were observed in peatland centers. Preventing anthropogenically derived surface or groundwater inputs from entering the peatland basin is essential for protecting peatland biodiversity and ecological functions. This can be accomplished by establishing natural vegetated buffers around contributing water features, removing stormwater inputs, and maintaining peatland watersheds with as much natural land cover as possible.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Genomic evidence for hybridization, mitochondrial capture and cryptic invasions in the Chinese mitten crab Eriocheir sinensis (Crustacea: Decapoda: Brachyura: Varunidae) - Joseph E. Ironside; Morag Taite; Natalie Cooper; Olivia Jones; Ben Wray; David Morritt; Paul F. Clark (Biological Invasions, 2025)
Enhanced genetic diversity arising from interspecific hybridisation and from multiple introductions from different source populations has played a major role in the evolution of invasive traits in introduced populations. Across Europe, mitochondrial haplotypes associated with the Japanese mitten crab Eriocheir japonica have been discovered in populations of the Chinese mitten crab Eriocheir sinensis, one of Europe’s highest priority aquatic invasive non-native species, suggesting a possible cryptic invasion of a second Eriocheir species. Analysis of the nuclear genomes of mitten crabs from one of these populations based on single nucleotide polymorphisms (SNPs) obtained through genotyping by sequencing, combined with landmark analysis of carapace morphology indicates that the crabs resemble E. sinensis in their morphology and nuclear genomic background, regardless of whether they carry an E. sinensis or E. japonica mitochondrial haplotype. This suggests interspecific introgression of mitochondrial DNA originating in the Japanese mitten crab Eriocheir japonica at some point in the population’s history, either in its native range or following introduction to Europe. A discrete cluster of SNP genotypes is associated with the E. japonica mitochondrial haplotype in samples from 2015 but not from 2020, suggesting an intraspecific cryptic invasion of genetically distinct mitten crabs into a previously established population, followed by interbreeding. Genetically diverse and novel hybrid biological invaders require particularly careful monitoring since they are likely to display enhanced evolutionary potential, with their life cycles and ecology possibly diverging from that of ancestral populations in their native range. In addition, mitochondrial environmental DNA and DNA barcoding of mitochondrial markers are increasingly relied upon to detect and identify aquatic non-native species. The potential for mitochondrial introgression between species to confuse these methods must be considered.

The Hippo effector TEAD1 regulates postnatal murine cerebellar development - Cooper Atterton; Alexandra Pelenyi; Justin Jones; Laura Currey; Majd Al-Khalily; Lucinda Wright; Mikki Doonan; David Knight; Nyoman D. Kurniawan; Shaun Walters; Stefan Thor; Michael Piper (Brain Structure and Function, 2025)
The Hippo signalling cascade is an evolutionarily conserved pathway critical for the development of numerous organ systems and is required for the development of many parts of the mammalian nervous system, including the cerebellum. The Hippo pathway converges, via the nuclear YAP/TAZ co-transcription factors, on transcription factors of the TEA Domain (TEAD) family (TEAD1-4) and promotes the expression of pro-proliferative genes. Despite the importance of TEAD function, our understanding of spatial and temporal expression of this family is limited, as is our understanding of which TEAD family members regulate Hippo-dependent organ development. Here, we focus on TEAD1 and how this factor contributes to postnatal murine cerebellar development. We find expression of TEAD1 within cerebellar progenitor cells and glial cells, including astrocytes and Bergmann glia, as well as by some interneurons within the granular layer. The importance of TEAD1 expression for cerebellar development was investigated using a conditional ablation approach, which revealed a range of developmental deficits in Tead1 mutants, including an underdeveloped cerebellum, morphological defects in Bergmann Glia and Purkinje Neurons, as well as granule neuron migration defects. Collectively, these findings suggest a major role for TEAD1 as an effector of the Hippo pathway during cerebellar development.

Critical assessment of missense variant effect predictors on disease-relevant variant data - Ruchir Rastogi; Ryan Chung; Sindy Li; Chang Li; Kyoungyeul Lee; Junwoo Woo; Dong-Wook Kim; Changwon Keum; Giulia Babbi; Pier Luigi Martelli; Castrense Savojardo; Rita Casadio; et al. (Human Genetics, 2025)
Regular, systematic, and independent assessments of computational tools that are used to predict the pathogenicity of missense variants are necessary to evaluate their clinical and research utility and guide future improvements. The Critical Assessment of Genome Interpretation (CAGI) conducts the ongoing Annotate-All-Missense (Missense Marathon) challenge, in which missense variant effect predictors (also called variant impact predictors) are evaluated on missense variants added to disease-relevant databases following the prediction submission deadline. Here we assess predictors submitted to the CAGI 6 Annotate-All-Missense challenge, predictors commonly used in clinical genetics, and recently developed deep learning methods. We examine performance across a range of settings relevant for clinical and research applications, focusing on different subsets of the evaluation data as well as high-specificity and high-sensitivity regimes. Our evaluations reveal notable advances in current methods relative to older, well-cited tools in the field. While meta-predictors tend to outperform their constituent individual predictors, several newer individual predictors perform comparably to commonly used meta-predictors. Predictor performance varies between high-specificity and high-sensitivity regimes, highlighting that different methods may be optimal for different use cases. We also characterize two potential sources of bias. Predictors that incorporate allele frequency as a predictive feature tend to have reduced performance when distinguishing pathogenic variants from very rare benign variants, and predictors trained on pathogenicity labels from curated variant databases often inherit gene-level label imbalances. Our findings help illuminate the clinical and research utility of modern missense variant effect predictors and identify potential areas for future development.

Review of phlegmacioid Cortinariaceae (Agaricales) in New Zealand - Karl Soop; Jerry A. Cooper; Andy R. Nilsen; Noah Siegel; David A. Orlovich (New Zealand Journal of Botany, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Avian diversity across guilds in North America versus vegetation structure as measured by the Global Ecosystem Dynamics Investigation (GEDI) - Jin Xu; Laura Farwell; Volker C. Radeloff; David Luther; Melissa Songer; William Justin Cooper; Qiongyu Huang (Remote Sensing of Environment, 2024)

Dynamics of two feed forward genetic motifs in the presence of molecular noise - Cooper Doe; David Brown; Hanqing Li (BioSystems, 2024)

Polymorphic pseudogenes in the human genome - a comprehensive assessment - Mónica Lopes-Marques; M. João Peixoto; David N. Cooper; M. João Prata; Luísa Azevedo; L. Filipe C. Castro (Human Genetics, 2024)
Background: Over the past decade, variations of the coding portion of the human genome have become increasingly evident. In this study, we focus on polymorphic pseudogenes, a unique and relatively unexplored type of pseudogene whose inactivating mutations have not yet been fixed in the human genome at the global population level. Thus, polymorphic pseudogenes are characterized by the presence in the population of both coding alleles and non-coding alleles originating from Loss-of-Function (LoF) mutations. These alleles can be found both in heterozygosity and in homozygosity in different human populations and thus represent pseudogenes that have not yet been fixed in the population. Results: A methodical cross-population analysis of 232 polymorphic pseudogenes, including 35 new examples, reveals that human olfactory signalling, drug metabolism and immunity are among the systems most impacted by the variable presence of LoF variants at high frequencies. Within this dataset, a total of 179 genes presented polymorphic LoF variants in all analysed populations. Transcriptome and proteome analysis confirmed that although these genes may harbour LoF alleles, when the coding allele is present, the gene remains active and can play a functional role in various metabolic pathways, including drug/xenobiotic metabolism and immunity. The observation that many polymorphic pseudogenes are members of multigene families argues that genetic redundancy may play a key role in compensating for the inactivation of one paralogue. Conclusions: The distribution, expression and integration of cellular/biological networks in relation to human polymorphic pseudogenes, provide novel insights into the architecture of the human genome and the dynamics of gene gain and loss with likely functional impact.

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Temporal trends of polycyclic aromatic hydrocarbons in soils amended with sludge, compost, and manure in a Scotland pasture: An 8-year field experiment - Xiao Ma; Patricia Cooper; Heliang Shi; Mark Osprey; David Riach; Graeme I. Paton; Qiao Xiong; Xiangjun Zhou; Zulin Zhang (Environmental Pollution, 2024)

VCAT: an integrated variant function annotation tools - Bi Huang; Cong Fan; Ken Chen; Jiahua Rao; Peihua Ou; Chong Tian; Yuedong Yang; David N. Cooper; Huiying Zhao (Human Genetics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genetic evidence for T-wave area from 12-lead electrocardiograms to monitor cardiovascular diseases in patients taking diabetes medications - Mengling Qi; Haoyang Zhang; Xuehao Xiu; Dan He; David N. Cooper; Yuanhao Yang; Huiying Zhao (Human Genetics, 2024)

Prospects for Neotropical Forest Birds and Their Habitats Under Contrasting Emissions Scenarios - Jeffrey D. Brawn; David Luther; Mingxin Qu; Sarah M. Farinelli; W. Justin Cooper; Rong Fu (Global Change Biology, 2024)
Current and near future climate policy will fundamentally influence the integrity of ecological systems. The Neotropics is a region where biodiversity is notably high and precipitation regimes largely determine the ecology of most organisms. We modeled possible changes in the severity of seasonal aridity by 2100 throughout the Neotropics and used birds to illustrate the implications of contrasting climate scenarios for the region's biodiversity. Under SSP‐8.5, a pessimistic and hopefully unlikely scenario, longer dry seasons (> 5%), and increased moisture stress are projected for about 75% of extant lowland forests throughout the entire region with impacts on 66% of the region's lowland forest avifauna, which comprises over 3000 species and about 30% of all bird species globally. Longer dry seasons are predicted to be especially significant in the Caribbean, Upper South America, and Amazonia. In contrast, under SSP‐2.6—a scenario with significant climate mitigation—only about 10% of the entire region's forest area and 3% of its avifauna will be exposed to longer dry seasons. The extent of current forest cover that may plausibly function as precipitation‐based climate refugia (i.e.,

An unusually large ‘suspension-feeding’ fish from the Kimmeridge Clay Formation of Dorset: the first true record of Asthenocormus (Pachycormiformes: Asthenocorminae) in the UK - Samuel L. A. Cooper; Erin E. Maxwell; David M. Martill (PalZ, 2024)
A partial caudal fin of a large-bodied asthenocormine pachycormiform (Pachycormiformes: Pachycormidae: Asthenocorminae) is described from the Upper Jurassic (lower Tithonian) Kimmeridge Clay Formation of Dorset, England. The specimen comprises associated fin rays, basal fulcra, ‘epurals’ and paired pre-caudal scutes, the combination and morphology of which is consistent with the large (2–3 m TL) edentulous, supposedly ‘suspension-feeding’ asthenocormine, Asthenocormus titanius (Wagner), presently known only from the Upper Jurassic plattenkalks of Bavaria, Germany. Asthenocormus has previously been documented in the literature as being present in the Middle and Upper Jurassic of England, however all of these specimens have been misattributed or since referred to different genera. However, the specimen from the Kimmeridge Clay Formation is here referred with confidence to Asthenocormus . Morphological variation in the pre-caudal dorsal scute of the new specimen compared to the Bavarian material suggest that the Kimmeridge Clay specimen likely represents a new species of Asthenocormus , although it is currently too poorly represented to diagnose, and hence we refer the specimen to Asthenocormus cf. titanius . The new specimen represents the first true record of Asthenocormus from the UK, thereby extending its known palaeobiogeographic distribution and further demonstrating faunal similarities between fish assemblage from the Kimmeridge Clay Formation of Dorset and the Solnhofen-type plattenkalks of southern Germany. Additional comments are also made on the hidden diversity of pachycormid fishes in the Kimmeridge Clay Formation.

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Modelling terrigenous DOC across the north west European Shelf: Fate of riverine input and impact on air-sea CO2 fluxes - Helen R. Powley; Luca Polimene; Ricardo Torres; Muchamad Al Azhar; Victoria Bell; David Cooper; Jason Holt; Sarah Wakelin; Yuri Artioli (Science of The Total Environment, 2024)

Equivocal support for the climate variability hypothesis within a N eotropical bird assemblage - Henry S. Pollock; Cameron L. Rutt; William Justin Cooper; Jeffrey D. Brawn; Zachary A. Cheviron; David A. Luther (Ecology, 2024)
The climate variability hypothesis posits that an organism's exposure to temperature variability determines the breadth of its thermal tolerance and has become an important framework for understanding variation in species' susceptibilities to climate change. For example, ectotherms from more thermally stable environments tend to have narrower thermal tolerances and greater sensitivity to projected climate warming. Among endotherms, however, the relationship between climate variability and thermal physiology is less clear, particularly with regard to microclimate variation—small‐scale differences within or between habitats. To address this gap, we explored associations between two sources of temperature variation (habitat type and vertical forest stratum) and (1) thermal physiological traits and (2) temperature sensitivity metrics within a diverse assemblage of Neotropical birds ( n = 89 species). We used long‐term temperature data to establish that daily temperature regimes in open habitats and forest canopy were both hotter and more variable than those in the forest interior and forest understory, respectively. Despite these differences in temperature regime, however, we found little evidence that species' thermal physiological traits or temperature sensitivity varied in association with either habitat type or vertical stratum. Our findings provide two novel and important insights. First, and in contrast to the supporting empirical evidence from ectotherms, the thermal physiology of birds at our study site appears to be largely decoupled from local temperature variation, providing equivocal support for the climate variability hypothesis in endotherms. Second, we found no evidence that the thermal physiology of understory forest birds differed from that of canopy or open‐habitat species—an oft‐invoked, yet previously untested, mechanism for why these species are so vulnerable to environmental change.

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Drivers and spatiotemporal patterns of post-drought growth resilience of four temperate broad-leaved trees - Liangjun Zhu; Jie Zhang; J. Julio Camarero; David J. Cooper; Paolo Cherubini; Danyang Yuan; Xiaochun Wang (Agricultural and Forest Meteorology, 2023)

Cortinarius subgenus Leprocybe (Agaricales) in New Zealand - Karl Soop; Jerry A. Cooper; Andy R. Nilsen; David A. Orlovich (New Zealand Journal of Botany, 2023)

Tree-ring data reveal trees are suffering from severe drought stress in the humid subtropical forest - Rong Zhang; Zihao Hu; Paolo Cherubini; David J. Cooper; Liangjun Zhu; Pifeng Lei (Forest Ecology and Management, 2023)

Effects of forest fragmentation on avian breeding activity - Charles P. J. Coddington; W. Justin Cooper; David A. Luther (Conservation Biology, 2023)
Biodiversity declines and ecosystem decay follow forest fragmentation; initially, abundant species may become rare or be extirpated. Underlying mechanisms behind delayed extirpation of certain species following forest fragmentation are unknown. Species declines may be attributed to an inadequate number of breeding adults required to replace the population or decreased juvenile survival rate due to reduced recruitment or increased nest predation pressures. We used 10 years of avian banding data, 5 years before and 4 years after fragment isolation, from the Biological Dynamics of Forest Fragments Project, carried out near Manaus, Brazil, to investigate the breeding activity hypothesis that there is less breeding activity and fewer young after relative to before fragment isolation. We compared the capture rates of active breeding and young birds in 3 forest types (primary forest, fragment before isolation, and fragment after isolation) and the proportion of active breeding and young birds with all birds in each unique fragment type before and after isolation. We grouped all bird species by diet (insectivore or frugivore) and nesting strategy (open cup, cavity, or enclosed) to allow further comparisons among forest types. We found support for the breeding activity hypothesis in insectivorous and frugivorous birds (effect sizes 0.45 and 0.53, respectively) and in birds with open‐cup and enclosed nesting strategies (effect sizes 0.56 and 0.44, respectively) such that on average there were more breeding birds in fragments before isolation relative to after isolation. A larger proportion of birds in the community were actively breeding before fragment isolation (72%) than after fragment isolation (11%). Unexpectedly, there was no significant decrease in the number of young birds after fragment isolation, although sample sizes for young were small ( n = 43). This may have been due to sustained immigration of young birds to fragments after isolation. Together, our results provide some of the strongest evidence to date that avian breeding activity decreases in response to fragment isolation, which could be a fundamental mechanism contributing to ecosystem decay.

Foreword to the Special Issue on Access and Benefit Sharing and Biological Control Genetic Resources - H. David Cooper (BioControl, 2023)

Agricultural practices drive elevated rates of topsoil decline across Kenya, but terracing and reduced tillage can reverse this - Christopher J. Feeney; David A. Robinson; Amy R.C. Thomas; Pasquale Borrelli; David M. Cooper; Linda May (Science of The Total Environment, 2023)

Biodegradation potential of residue generated during the in-situ burning of oil in the marine environment - Ruby Pyke; Nathalie Fortin; Jessica Wasserscheid; Julien Tremblay; Lars Schreiber; Marie-Josee Levesque; Stephanie Messina-Pacheco; Lyle Whyte; Feiyue Wang; Kenneth Lee; David Cooper; Charles W. Greer (Journal of Hazardous Materials, 2023)

An age-depth model and revised stratigraphy of vertebrate-bearing units in Natural Trap Cave, Wyoming - David M. Lovelace; Cory M. Redman; Thomas A. Minckley; Blaine W. Schubert; Shannon Mahan; John R. Wood; Jenny L. McGuire; Juan Laden; Kathleen Bitterman; Holly Heiniger; Lindsey Fenderson; Alan Cooper; et al. (Quaternary International, 2023)

Identifying shared genetic factors underlying epilepsy and congenital heart disease in Europeans - Yiming Wu; Cigdem Sevim Bayrak; Bosi Dong; Shixu He; Peter D. Stenson; David N. Cooper; Yuval Itan; Lei Chen (Human Genetics, 2023)

Profiling human pathogenic repeat expansion regions by synergistic and multi-level impacts on molecular connections - Cong Fan; Ken Chen; Yukai Wang; Edward V. Ball; Peter D. Stenson; Matthew Mort; Albino Bacolla; Hildegard Kehrer-Sawatzki; John A. Tainer; David N. Cooper; Huiying Zhao (Human Genetics, 2023)

Towards an understanding of future range shifts in lichens and mosses under climate change - Max Mallen‐Cooper; Emilio Rodríguez‐Caballero; David J. Eldridge; Bettina Weber; Burkhard Büdel; Hermann Höhne; Will K. Cornwell (Journal of Biogeography, 2023)
Aim Lichens and mosses play important functional roles in all terrestrial ecosystems, particularly in tundra and drylands. As with all taxa, to maintain their current niche in a changing climate, lichens and mosses will have to migrate. However, there are no published estimates of future habitat suitability or necessary rates of migration for members of these groups at the global scale. Taxon Lichens and mosses. Location Global. Methods Using global occurrence data, we conducted ensemble distribution models in the ‘biomod2’ R package, parameterised with a range of climatic, land use and soil variables, to estimate current and future (2100) habitat suitability in 16 abundant species of lichen and moss. Results Without considering dispersal limitation, suitable area was forecast to expand for eight species and decline for four species. For species with predominantly boreo‐arctic distributions, suitable area typically declined at the temperate range edge and expanded across the High Arctic. Future suitable area available to dryland‐adapted species generally declined overall, likely relating to the desiccation‐tolerant physiology of lichens and mosses. The average migration rates required for species to disperse into new suitable habitat ranged from 1.7 ( Placidium squamulosum ) to 9.0 km year −1 ( Syntrichia ruralis ), although most species will need to migrate >16 km year −1 to completely fill their potential future suitable habitat. Main Conclusions For mosses and lichens, as with all species, migration will be an important part of the adjustment to a warmer climate, but realisation of these potential migrations will require both rare dispersal events and habitat that is suitable in non‐climatic dimensions. Current evidence on dispersal in these groups suggests that these geographical shifts may be unlikely to be realised without intervention, especially in landscapes that are highly modified by humans.

Trypsinogen (PRSS1 and PRSS2) gene dosage correlates with pancreatitis risk across genetic and transgenic studies: a systematic review and re-analysis - Wen-Bin Zou; David N. Cooper; Emmanuelle Masson; Na Pu; Zhuan Liao; Claude Férec; Jian-Min Chen (Human Genetics, 2022)

Global synthesis reveals strong multifaceted effects of eucalypts on soils - Max Mallen‐Cooper; Joe Atkinson; Zoe A. Xirocostas; Baptiste Wijas; Giancarlo M. Chiarenza; Frederick A. Dadzie; David J. Eldridge (Global Ecology and Biogeography, 2022)
Aim Eucalypts have a widespread global distribution owing to their popularity for agroforestry and as environmental plantings. Despite an abundance of site‐specific evidence that eucalypts modify soils and soil processes, we lack a quantitative synthesis of their overall effects at the global scale. This limits our capacity to assess the likely impacts of future introductions in any given region of the world. Location Global. Time period 1986–2021. Major taxa studied Eucalyptus , Angophora and Corymbia . Methods We used a systematic search to derive a database of empirical data from 227 studies across 33 countries ( n effect size = 2,806) and tested three predictions about the effects of eucalypts on soil properties and whether these effects varied with plantation age and soil depth. Results Compared with (non‐eucalypt) native vegetation, eucalypts significantly reduced soil moisture, microbial abundance, nitrogen, cations and anions. Relative reductions in soil microbes and ions were stronger in older eucalypt plantations. A comparison of eucalypts with (non‐eucalypt) silvicultural and agropastoral systems revealed similar effects on most soil properties, although eucalypts tended to reduce potassium and enhance carbon to a greater extent than other managed systems. We found no consistent effects of eucalypts on soil pH. Main conclusions Our study provides the first extensive global meta‐analysis of the effects of eucalypts on soil properties and processes and demonstrates that effects are highly dependent on the community with which they are compared (i.e., natural or managed). In general, our findings reinforce the widely held belief that eucalypts deplete soil nutrients and dominate water resources. Understanding how eucalypts affect soils allows us to assess their global suitability for agroforestry, soil rehabilitation and soil carbon enhancement, while considering the potential environmental costs.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Climatic controls of Pinus pumila radial growth along an altitude gradient - Jingwen Yang; David J. Cooper; Xu Zhang; Wenqi Song; Zongshan Li; Yuandong Zhang; Huiying Zhao; Shijie Han; Xiaochun Wang (New Forests, 2022)

Multi-species approach strengthens the reliability of dendroclimatic reconstructions in monsoonal Northeast China - Liangjun Zhu; Shuguang Liu; Haifeng Zhu; David J. Cooper; Danyang Yuan; Yu Zhu; Zongshan Li; Yuandong Zhang; Hanxue Liang; Xu Zhang; Wenqi Song; Xiaochun Wang (Climatic Change, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Challenges in the diagnosis of neurofibromatosis type 1 (NF1) in young children facilitated by means of revised diagnostic criteria including genetic testing for pathogenic NF1 gene variants - Hildegard Kehrer-Sawatzki; David N. Cooper (Human Genetics, 2022)
Neurofibromatosis type 1 (NF1) is the most frequent disorder associated with multiple café-au-lait macules (CALM) which may either be present at birth or appear during the first year of life. Other NF1-associated features such as skin-fold freckling and Lisch nodules occur later during childhood whereas dermal neurofibromas are rare in young children and usually only arise during early adulthood. The NIH clinical diagnostic criteria for NF1, established in 1988, include the most common NF1-associated features. Since many of these features are age-dependent, arriving at a definitive diagnosis of NF1 by employing these criteria may not be possible in infancy if CALM are the only clinical feature evident. Indeed, approximately 46% of patients who are diagnosed with NF1 later in life do not meet the NIH diagnostic criteria by the age of 1 year. Further, the 1988 diagnostic criteria for NF1 are not specific enough to distinguish NF1 from other related disorders such as Legius syndrome. In this review, we outline the challenges faced in diagnosing NF1 in young children, and evaluate the utility of the recently revised (2021) diagnostic criteria for NF1, which include the presence of pathogenic variants in the NF1 gene and choroidal anomalies, for achieving an early and accurate diagnosis.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Classification of NF1 microdeletions and its importance for establishing genotype/phenotype correlations in patients with NF1 microdeletions - Hildegard Kehrer-Sawatzki; David N. Cooper (Human Genetics, 2021)
An estimated 5–11% of patients with neurofibromatosis type-1 (NF1) harbour large deletions encompassing the NF1 gene and flanking regions. These NF1 microdeletions are subclassified into type 1, 2, 3 and atypical deletions which are distinguishable from each other by their extent and by the number of genes included within the deletion regions as well as the frequency of mosaicism with normal cells. Most common are type-1 NF1 deletions which encompass 1.4-Mb and 14 protein-coding genes. Type-1 deletions are frequently associated with overgrowth, global developmental delay, cognitive disability and dysmorphic facial features which are uncommon in patients with intragenic pathogenic NF1 gene variants. Further, patients with type-1 NF1 deletions frequently exhibit high numbers of neurofibromas and have an increased risk of malignant peripheral nerve sheath tumours. Genes located within the type-1 NF1 microdeletion interval and co-deleted with NF1 are likely to act as modifiers responsible for the severe disease phenotype in patients with NF1 microdeletions, thereby causing the NF1 microdeletion syndrome. Genotype/phenotype correlations in patients with NF1 microdeletions of different lengths are important to identify such modifier genes. However, these correlations are critically dependent upon the accurate characterization of the deletions in terms of their extent. In this review, we outline the utility as well as the shortcomings of multiplex ligation-dependent probe amplification (MLPA) to classify the different types of NF1 microdeletion and indicate the importance of high-resolution microarray analysis for correct classification, a necessary precondition to identify those genes responsible for the NF1 microdeletion syndrome.

Distinct patterns of resting-state connectivity in U.S. service members with mild traumatic brain injury versus posttraumatic stress disorder - Carissa L. Philippi; Carmen S. Velez; Benjamin S.C. Wade; Ann Marie Drennon; Douglas B. Cooper; Jan E. Kennedy; Amy O. Bowles; Jeffrey D. Lewis; Matthew W. Reid; Gerald E. York; Mary R. Newsome; Elisabeth A. Wilde; et al. (Brain Imaging and Behavior, 2021)

Biodegradation, Bioaccumulation and Toxicity of Oil Spill Herding Agents in Arctic Waters as Part of an Ecotoxicological Screening - Janne Fritt-Rasmussen; Eva Friis Møller; Line Anker Kyhn; Susse Wegeberg; Pia Lassen; David Cooper; Kim Gustavson (Water, Air, & Soil Pollution, 2021)

Compensatory epistasis explored by molecular dynamics simulations - Catarina Serrano; Carla S. S. Teixeira; David N. Cooper; João Carneiro; Mónica Lopes-Marques; Peter D. Stenson; António Amorim; Maria J. Prata; Sérgio F. Sousa; Luísa Azevedo (Human Genetics, 2021)

Circulating level of Angiopoietin-2 is associated with acute kidney injury in coronavirus disease 2019 (COVID-19) - Brandon Michael Henry; Maria Helena Santos de Oliveira; Isaac Cheruiyot; Justin L. Benoit; David S. Cooper; Giuseppe Lippi; Timothy D. Le Cras; Stefanie W. Benoit (Angiogenesis, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Historical overview and new directions in bioarchaeological trace element analysis: a review - Rachel Simpson; David M. L. Cooper; Treena Swanston; Ian Coulthard; Tamara L. Varney (Archaeological and Anthropological Sciences, 2021)
Given their strong affinity for the skeleton, trace elements are often stored in bones and teeth long term. Diet, geography, health, disease, social status, activity, and occupation are some factors which may cause differential exposure to, and uptake of, trace elements, theoretically introducing variability in their concentrations and/or ratios in the skeleton. Trace element analysis of bioarchaeological remains has the potential, therefore, to provide rich insights into past human lifeways. This review provides a historical overview of bioarchaeological trace element analysis and comments on the current state of the discipline by highlighting approaches with growing momentum. Popularity for the discipline surged following preliminary studies in the 1960s to 1970s that demonstrated the utility of strontium (Sr) as a dietary indicator. During the 1980s, Sr/Ca ratio and multi-element studies were commonplace in bioarchaeology, linking trace elements with dietary phenomena. Interest in using trace elements for bioarchaeological inferences waned following a period of critiques in the late 1980s to 1990s that argued the discipline failed to account for diagenesis, simplified complex element uptake and regulation processes, and used several unsuitable elements for palaeodietary reconstruction (e.g. those under homeostatic regulation, those without a strong affinity for the skeleton). In the twenty-first century, trace element analyses have been primarily restricted to Sr and lead (Pb) isotope analysis and the study of toxic trace elements, though small pockets of bioarchaeology have continued to analyse multiple elements. Techniques such as micro-sampling, element mapping, and non-traditional stable isotope analysis have provided novel insights which hold the promise of helping to overcome limitations faced by the discipline.

Using Vegetation Guilds to Predict Bird Habitat Characteristics in Riparian Areas - Erin S. Cubley; Heather L. Bateman; David M. Merritt; David J. Cooper (Wetlands, 2020)

Wetland Plant Communities of the Eastern Himalayan Highlands in Northern Bhutan - Pema Tendar; David J. Cooper; Kitichate Sridith (Wetlands, 2020)

Comparison of USACE Three-Factor Wetland Delineations to National Wetland Inventory Maps - Edward Gage; David J. Cooper; Robert Lichvar (Wetlands, 2020)

The Human Gene Mutation Database (HGMD®): optimizing its use in a clinical diagnostic or research setting - Peter D. Stenson; Matthew Mort; Edward V. Ball; Molly Chapman; Katy Evans; Luisa Azevedo; Matthew Hayden; Sally Heywood; David S. Millar; Andrew D. Phillips; David N. Cooper (Human Genetics, 2020)
The Human Gene Mutation Database (HGMD ® ) constitutes a comprehensive collection of published germline mutations in nuclear genes that are thought to underlie, or are closely associated with human inherited disease. At the time of writing (June 2020), the database contains in excess of 289,000 different gene lesions identified in over 11,100 genes manually curated from 72,987 articles published in over 3100 peer-reviewed journals. There are primarily two main groups of users who utilise HGMD on a regular basis; research scientists and clinical diagnosticians. This review aims to highlight how to make the most out of HGMD data in each setting.

Cases of foreign egg adoption by Brown Skuas Stercorarius antarcticus on Marion and Gough Islands - Alexis Osborne; Christopher W. Jones; Michelle M. Risi; David B. Green; Ben J. Dilley; John Cooper (Polar Biology, 2020)

Soils and Hydrologic Processes Drive Wet Meadow Formation and Approaches to Restoration, Western USA - Derek M. Schook; Andrea K. Borkenhagen; Paul A. McDaniel; Joel I. Wagner; David J. Cooper (Wetlands, 2020)

Evaluating the realized niche and plant–water relations of wetland species using experimental transplants - Jeremy P. Sueltenfuss; Troy W. Ocheltree; David J. Cooper (Plant Ecology, 2020)

Dynamics of dissolved organic matter in headwaters: comparison of headwater streams with contrasting DOM and nutrient composition - Ophelie Fovet; David M. Cooper; Davey L. Jones; Timothy G. Jones; Chris D. Evans (Aquatic Sciences, 2020)

Effectiveness of control strategies for Varroa jacobsoni and Tropilaelaps mercedesae in Papua New Guinea - John M. K. Roberts; Cooper N. Schouten; Reuben W. Sengere; John Jave; David Lloyd (Experimental and Applied Acarology, 2020)

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

A comparison of air sampling methods for Clostridium difficile endospore aerosol - Casey W. Cooper; Kathleen A. N. Aithinne; Evan L. Floyd; Bradley S. Stevenson; David L. Johnson (Aerobiologia, 2019)

The Weed Link in Zebra Chip Epidemiology: Suitability of Non-crop Solanaceae and Convolvulaceae to Potato Psyllid and “Candidatus Liberibacter Solanacearum” - W. Rodney Cooper; David R. Horton; Eugene Miliczky; Carrie H. Wohleb; Timothy D. Waters (American Journal of Potato Research, 2019)

Recognition of the discipline of conservation mycology - Tom W. May; Jerry A. Cooper; Anders Dahlberg; Giuliana Furci; David W. Minter; Gregory M. Mueller; Alison Pouliot; Zhuliang Yang (Conservation Biology, 2019)
Article impact statement : Conservation mycology is a newly introduced discipline relevant to conservation biologists, mycologists, ecologists, and conservation policy.

Global meta‐analysis of soil‐disturbing vertebrates reveals strong effects on ecosystem patterns and processes - Max Mallen‐Cooper; Shinichi Nakagawa; David J. Eldridge (Global Ecology and Biogeography, 2019)
Aim Organisms that disturb the soil while foraging or creating shelter (ecosystem engineers) can have profound effects on ecosystems. Soil ejecta from these disturbances can enhance surface nutrients and the resulting depressions accrue organic matter and develop into biological hotspots. Here, we describe a global meta‐analysis of studies that assessed the impacts of vertebrate soil disturbance on both biotic and abiotic components of ecosystems. Location Global land surface. Time period 1941–2016. Major taxa studied Vertebrates. Methods After conducting a systematic literature search, we quantitatively synthesized the findings of 149 published studies that compared disturbed and undisturbed surfaces. Our meta‐analysis included 64 engineer species, primarily comprised of rodents and a subset of other mammals. Results We found that vertebrate soil disturbance significantly enhanced soil nitrogen (by 77%) and phosphorus (35%), and the productivity (32%) and recruitment (32%) of vascular plants. Disturbances had a greater cover of bare soil (126%) than undisturbed controls, and higher abundances of secondary vertebrates (1,233%), that use pre‐constructed burrows as shelter and foraging grounds. Soil disturbance significantly reduced water run‐off (63%) and the abundance of biocrusts (82%). Soil disturbance effects generally intensified with increasing aridity, and the magnitude of soil disturbance effects was not moderated by the area of the disturbance. Disturbances older than 12 months were more distinct from the surrounding matrix than fresh disturbances. The phylogeny of engineers was unrelated to their ecosystem effects, indicating that the same functionality could readily evolve in different taxa. Main conclusions In general, disturbances become localized patches of elevated functioning, providing strong evidence that vertebrate engineers, especially those in drylands, are an important source of environmental heterogeneity.

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Ultra-deep amplicon sequencing indicates absence of low-grade mosaicism with normal cells in patients with type-1 NF1 deletions - Anna Summerer; Eleonora Schäfer; Victor-Felix Mautner; Ludwine Messiaen; David N. Cooper; Hildegard Kehrer-Sawatzki (Human Genetics, 2019)

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

What can seabirds tell us about the tide? - Matthew Cooper; Charles Bishop; Matthew Lewis; David Bowers; Mark Bolton; Ellie Owen; Stephen Dodd (Ocean Science, 2018)
Small global positioning system (GPS) trackers are now routinely used to study the movement and behaviour of birds at sea. If the birds rest on the water they become “drifters of opportunity” and can be used to give information about surface currents. In this paper, we use a small data set from satellite-tracked razorbills (Alca torda) in the Irish Sea to test the potential of this idea for measuring tidal currents. Razorbills regularly rest on the sea overnight and their tracks at this time are consistent with their drifting with the tidal flows and changing direction as the flood turns to ebb and vice versa. Data from 4 years (2011–2014) have been binned in a geographical grid and analysed to give the variation of current over a mean tidal cycle in each grid element. A map of maximum current speed is consistent with a numerical model of the tidal currents in the region. The root mean square difference between observed maximum speed and that predicted by the model is 0.15 m s−1, about 15 % of typical current speeds in the area. The divergence between bird-track speed and model prediction increases in regions of the fastest tidal currents. The method clearly has its limitations, but the results of this study show that tagged birds resting on the sea have potential to provide relatively inexpensive quantitative information about surface tidal currents over an extended geographical area.

Seasonal and diurnal surveillance of treated and untreated wastewater for human enteric viruses - Kata Farkas; Miles Marshall; David Cooper; James E. McDonald; Shelagh K. Malham; Dafydd E. Peters; John D. Maloney; Davey L. Jones (Environmental Science and Pollution Research, 2018)

Stoichiometric constraints on the microbial processing of carbon with soil depth along a riparian hillslope - Laura L. de Sosa; Helen C. Glanville; Miles R. Marshall; Andrea Schnepf; David M. Cooper; Paul W. Hill; Andrew Binley; Davey L. Jones (Biology and Fertility of Soils, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

A comparison of the taxonomic and trait structure of macroinvertebrate communities between the riffles and pools of montane headwater streams - David B. Herbst; Scott D. Cooper; R. Bruce Medhurst; Sheila W. Wiseman; Carolyn T. Hunsaker (Hydrobiologia, 2018)

Livestock grazing and aridity reduce the functional diversity of biocrusts - Max Mallen-Cooper; David J. Eldridge; Manuel Delgado-Baquerizo (Plant and Soil, 2018)

Phenotypic and genotypic overlap between mosaic NF2 and schwannomatosis in patients with multiple non-intradermal schwannomas - Hildegard Kehrer-Sawatzki; Lan Kluwe; Reinhard E. Friedrich; Anna Summerer; Eleonora Schäfer; Ute Wahlländer; Cordula Matthies; Isabel Gugel; Said Farschtschi; Christian Hagel; David N. Cooper; Victor-Felix Mautner (Human Genetics, 2018)

Extreme clustering of type-1 NF1 deletion breakpoints co-locating with G-quadruplex forming sequences - Anna Summerer; Victor-Felix Mautner; Meena Upadhyaya; Kathleen B. M. Claes; Josef Högel; David N. Cooper; Ludwine Messiaen; Hildegard Kehrer-Sawatzki (Human Genetics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Inter- and intra-species intercropping of barley cultivars and legume species, as affected by soil phosphorus availability - Tegan Darch; Courtney D. Giles; Martin S. A. Blackwell; Timothy S. George; Lawrie K. Brown; Daniel Menezes-Blackburn; Charles A. Shand; Marc I. Stutter; David G. Lumsdon; Malika M. Mezeli; Renate Wendler; Hao Zhang; et al. (Plant and Soil, 2018)

Opportunities for mobilizing recalcitrant phosphorus from agricultural soils: a review - Daniel Menezes-Blackburn; Courtney Giles; Tegan Darch; Timothy S. George; Martin Blackwell; Marc Stutter; Charles Shand; David Lumsdon; Patricia Cooper; Renate Wendler; Lawrie Brown; Danilo S. Almeida; et al. (Plant and Soil, 2018)

Pronounced maternal parent-of-origin bias for type-1 NF1 microdeletions - Lisa Neuhäusler; Anna Summerer; David N. Cooper; Victor-F. Mautner; Hildegard Kehrer-Sawatzki (Human Genetics, 2018)

Pharmacological inhibition of the NLRP3 inflammasome as a potential target for multiple sclerosis induced central neuropathic pain - Nemat Khan; Andy Kuo; David A. Brockman; Matthew A. Cooper; Maree T. Smith (Inflammopharmacology, 2018)

Relationships between landscape pattern metrics, vertical structure and surface urban Heat Island formation in a Colorado suburb - Edward A. Gage; David J. Cooper (Urban Ecosystems, 2017)

Altitude profile of the OH radical complex with water in Earth’s atmosphere: a quantum mechanical approach - David Voglozin; Paul Cooper (Journal of Atmospheric Chemistry, 2017)

Association of Potato Psyllid (Bactericera cockerelli; Hemiptera: Triozidae) with Lycium spp. (Solanaceae) in Potato Growing Regions of Washington, Idaho, and Oregon - Jenita Thinakaran; David R. Horton; W. Rodney Cooper; Andrew S. Jensen; Carrie H. Wohleb; Jennifer Dahan; Tariq Mustafa; Alexander V. Karasev; Joseph E. Munyaneza (American Journal of Potato Research, 2017)

regSNPs-splicing: a tool for prioritizing synonymous single-nucleotide substitution - Xinjun Zhang; Meng Li; Hai Lin; Xi Rao; Weixing Feng; Yuedong Yang; Matthew Mort; David N. Cooper; Yue Wang; Yadong Wang; Clark Wells; Yaoqi Zhou; et al. (Human Genetics, 2017)

Growing season carbon gas exchange from peatlands used as a source of vegetation donor material for restoration - Kimberley R. Murray; Andrea K. Borkenhagen; David J. Cooper; Maria Strack (Wetlands Ecology and Management, 2017)

Environmental drivers of subalpine and alpine fen vegetation in the Southern Rocky Mountains, Colorado, USA - Betsy L. Harbert; David J. Cooper (Plant Ecology, 2017)

The Human Gene Mutation Database: towards a comprehensive repository of inherited mutation data for medical research, genetic diagnosis and next-generation sequencing studies - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Evans; Matthew Hayden; Sally Heywood; Michelle Hussain; Andrew D. Phillips; David N. Cooper (Human Genetics, 2017)

Emerging genotype–phenotype relationships in patients with large NF1 deletions - Hildegard Kehrer-Sawatzki; Victor-Felix Mautner; David N. Cooper (Human Genetics, 2017)

Does the combination of citrate and phytase exudation in Nicotiana tabacum promote the acquisition of endogenous soil organic phosphorus? - Courtney D. Giles; Timothy S. George; Lawrie K. Brown; Malika M. Mezeli; Alan E. Richardson; Charles A. Shand; Renate Wendler; Tegan Darch; Daniel Menezes-Blackburn; Patricia Cooper; Marc I. Stutter; David G. Lumsdon; et al. (Plant and Soil, 2017)

Mountain Peatlands Range from CO2 Sinks at High Elevations to Sources at Low Elevations: Implications for a Changing Climate - David J. Millar; David J. Cooper; Kathleen A. Dwire; Robert M. Hubbard; Joseph von Fischer (Ecosystems, 2017)

The molecular pathogenesis of schwannomatosis, a paradigm for the co-involvement of multiple tumour suppressor genes in tumorigenesis - Hildegard Kehrer-Sawatzki; Said Farschtschi; Victor-Felix Mautner; David N. Cooper (Human Genetics, 2017)

HPLC-MS Analysis of Lichen-Derived Metabolites in the Life Stages of Crambidia cephalica (Grote & Robinson) - Timothy J. Anderson; David L. Wagner; Bruce R. Cooper; Megan E. McCarty; Jennifer M. Zaspel (Journal of Chemical Ecology, 2017)

Organic farmers’ motivations and challenges for adopting conservation agriculture in Europe - Marion Casagrande; Joséphine Peigné; Vincent Payet; Paul Mäder; F. Xavier Sans; José Manuel Blanco-Moreno; Daniele Antichi; Paolo Bàrberi; Annelies Beeckman; Federica Bigongiali; Julia Cooper; Hansueli Dierauer; et al. (Organic Agriculture, 2016)

Laboratory-based techniques for assessing the functional traits of biocrusts - Max Mallen-Cooper; David J. Eldridge (Plant and Soil, 2016)

Persistence of high elevation fens in the Southern Rocky Mountains, on Grand Mesa, Colorado, U.S.A. - Gay Austin; David J. Cooper (Wetlands Ecology and Management, 2016)

Short-term effect of nitrogen addition on nitric oxide emissions from an alpine meadow in the Tibetan Plateau - Yongheng Gao; Xingxing Ma; David J. Cooper (Environmental Science and Pollution Research, 2016)

Potentially inappropriate prescribing in two populations with differing socio-economic profiles: a cross-sectional database study using the PROMPT criteria - Janine A. Cooper; Frank Moriarty; Cristín Ryan; Susan M. Smith; Kathleen Bennett; Tom Fahey; Emma Wallace; Caitriona Cahir; David Williams; Mary Teeling; Carmel M. Hughes (European Journal of Clinical Pharmacology, 2016)

Isolation and characterization of Bradyrhizobium sp. SR1 degrading two β-triketone herbicides - Sana Romdhane; Marion Devers-Lamrani; Fabrice Martin-Laurent; Christophe Calvayrac; Emilie Rocaboy-Faquet; David Riboul; Jean-François Cooper; Lise Barthelmebs (Environmental Science and Pollution Research, 2016)

Developing a Field-Tested Wetland Indicator Rating for Blue Spruce (Picea Pungens) in the Southern Rocky Mountains - Edward A. Gage; David J. Cooper; Betsy Bultema; Cristina McKernan; Robert Lichvar (Wetlands, 2016)

Treatment of persistent post-concussive symptoms after mild traumatic brain injury: a systematic review of cognitive rehabilitation and behavioral health interventions in military service members and veterans - Douglas B. Cooper; Anne E. Bunner; Jan E. Kennedy; Valerie Balldin; David F. Tate; Blessen C. Eapen; Carlos A. Jaramillo (Brain Imaging and Behavior, 2015)

Subgroups of US IRAQ and Afghanistan veterans: associations with traumatic brain injury and mental health conditions - Carlos A. Jaramillo; Douglas B. Cooper; Chen-Pin Wang; David F. Tate; Blessen C. Eapen; Gerald E. York; Mary Jo Pugh (Brain Imaging and Behavior, 2015)

The Influence of Land Cover, Vertical Structure, and Socioeconomic Factors on Outdoor Water Use in a Western US City - Edward Gage; David J. Cooper (Water Resources Management, 2015)

Erratum to: The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Temporal and spatial availability of A tlantic T hread H erring, O pisthonema oglinum , in relation to oceanographic drivers and fishery landings on the Florida Panhandle - David Chagaris; Behzad Mahmoudi; Frank Muller‐Karger; Wade Cooper; Keith Fischer (Fisheries Oceanography, 2015)
Since 1995, landings of Atlantic Thread Herring ( Opisthonema oglinum ) on the Florida Panhandle averaged 124 mt each spring (April–June) but declined to nearly zero in 1996–97 and 2006. To elucidate causes of recurring periods of low landings, we used generalized additive mixed models ( GAMM s) to examine the relationship between Atlantic Thread Herring catch in a trawl survey on the west‐central coast of Florida and four environmental variables. Chlorophyll‐ a was significant in the models, indicating a direct relationship between local abundance of baitfish and their planktonic food. Temperature and depth were also significant whereas salinity was not. During 2003 and 2012, synoptic satellite‐derived temperature and chlorophyll‐ a maps were used with the GAMM s to predict monthly spatial availability on the Florida Panhandle fishing grounds (long. 85–88 o W and depth 12–25 m). The predicted monthly availability was significantly correlated with commercial catch rates (Pearson's r = 0.26, P = 0.004, d.f. = 118). We used multiple linear regression ( MLR ) with lags to describe the effect of river discharge and wind (as a transport mechanism) on surface chlorophyll‐ a over the Panhandle fishing grounds. Discharge from local rivers was significant in all MLR s, and the Mississippi was only significant as an interaction with wind. We conclude that Atlantic Thread Herring are distributed over the Panhandle fishing grounds based on food availability that is driven by river discharge and eastward transport of Mississippi River plumes. This analysis improves our understating of baitfish dynamics, an important ecosystem component in the Gulf of Mexico.

Determining the timing of willow shrub dieback using epicormic shoots - Kristen M. Kaczynski; David J. Cooper (Wetlands Ecology and Management, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Genetic Data Sharing and Privacy - Marco D. Sorani; John K. Yue; Sourabh Sharma; Geoffrey T. Manley; Adam R. Ferguson; Shelly R. Cooper; Kristen Dams-O’Connor; Wayne A. Gordon; Hester F. Lingsma; Andrew I. R. Maas; David K. Menon; Diane J. Morabito; et al. (Neuroinformatics, 2015)

Infilled Ditches are Hotspots of Landscape Methane Flux Following Peatland Re-wetting - Mark. D. A. Cooper; Christopher. D. Evans; Piotr Zielinski; Peter. E. Levy; Alan Gray; Mike Peacock; David Norris; Nathalie Fenner; Christopher Freeman (Ecosystems, 2014)

Using palaeoenvironmental DNA to reconstruct past environments: progress and prospects - NICOLAS J. RAWLENCE; DAVID J. LOWE; JAMIE R. WOOD; JENNIFER M. YOUNG; G. JOCK CHURCHMAN; YU‐TUAN HUANG; ALAN COOPER (Journal of Quaternary Science, 2014)
Palaeoenvironmental DNA (PalEnDNA) is defined as ancient DNA (aDNA) originating from disseminated genetic material within palaeoenvironmental samples. Sources of PalEnDNA include marine and lake sediments, peat, loess, till, ice, permafrost, palaeosols, coprolites, preserved gut contents, dental calculus, tephras, and soils as well as deposits in caves/rockshelters and at archaeological sites. PalEnDNA analysis provides a relatively new tool for Quaternary and archaeological sciences and its applications have included palaeoenvironmental and palaeodietary reconstructions, testing hypotheses regarding megafaunal extinctions, human–environment interactions, taxonomic studies, and studies of DNA damage. Because PalEnDNA samples comprise markedly different materials, and represent wide‐ranging depositional and taphonomic contexts, various issues must be addressed to achieve robust, reproducible findings. Such issues include climatic and temporal limitations, the biological origin and state (free versus bound) of PalEnDNA, stratigraphic reliability, sterile sampling, ability to distinguish modern from aDNA signals, DNA damage and PCR amplification, DNA extraction methods, and taxonomic resolution. In this review, we provide a non‐specialist introduction to the use of PalEnDNA for Quaternary and archaeological researchers, assess attributes and limitations of this palaeoenvironmental tool, and discuss future prospects of using PalEnDNA to reconstruct past environments.

Assessing Risk to Birds from Industrial Wind Energy Development via Paired Resource Selection Models - TRICIA A. MILLER; ROBERT P. BROOKS; MICHAEL LANZONE; DAVID BRANDES; JEFF COOPER; KIERAN O'MALLEY; CHARLES MAISONNEUVE; JUNIOR TREMBLAY; ADAM DUERR; TODD KATZNER (Conservation Biology, 2014)
When wildlife habitat overlaps with industrial development animals may be harmed. Because wildlife and people select resources to maximize biological fitness and economic return, respectively, we estimated risk, the probability of eagles encountering and being affected by turbines, by overlaying models of resource selection for each entity. This conceptual framework can be applied across multiple spatial scales to understand and mitigate impacts of industry on wildlife. We estimated risk to Golden Eagles (Aquila chrysaetos) from wind energy development in 3 topographically distinct regions of the central Appalachian Mountains of Pennsylvania (United States) based on models of resource selection of wind facilities (n = 43) and of northbound migrating eagles (n = 30). Risk to eagles from wind energy was greatest in the Ridge and Valley region; all 24 eagles that passed through that region used the highest risk landscapes at least once during low altitude flight. In contrast, only half of the birds that entered the Allegheny Plateau region used highest risk landscapes and none did in the Allegheny Mountains. Likewise, in the Allegheny Mountains, the majority of wind turbines (56%) were situated in poor eagle habitat; thus, risk to eagles is lower there than in the Ridge and Valley, where only 1% of turbines are in poor eagle habitat. Risk within individual facilities was extremely variable; on average, facilities had 11% (SD 23; range = 0–100%) of turbines in highest risk landscapes and 26% (SD 30; range = 0–85%) of turbines in the lowest risk landscapes. Our results provide a mechanism for relocating high‐risk turbines, and they show the feasibility of this novel and highly adaptable framework for managing risk of harm to wildlife from industrial development. Evaluación del Riesgo para las Aves por el Desarrollo de Energía Eólica Industrial Mediante Modelos de Selección de Recursos Pareados.

Population-specific differences in gene conversion patterns between human SUZ12 and SUZ12P are indicative of the dynamic nature of interparalog gene conversion - Tanja Mussotter; Kathrin Bengesser; Josef Högel; David N. Cooper; Hildegard Kehrer-Sawatzki (Human Genetics, 2014)

The emergence of the mitochondrial genome as a partial regulator of nuclear function is providing new insights into the genetic mechanisms underlying age-related complex disease - Martin P. Horan; David N. Cooper (Human Genetics, 2014)

Nutrient mitigation in a temporary river basin - Ourania Tzoraki; Nikolaos P. Nikolaidis; David Cooper; Elissavet Kassotaki (Environmental Monitoring and Assessment, 2014)

The Human Gene Mutation Database: building a comprehensive mutation repository for clinical and molecular genetics, diagnostic testing and personalized genomic medicine - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Shaw; Andrew D. Phillips; David N. Cooper (Human Genetics, 2014)
The Human Gene Mutation Database (HGMD ® ) is a comprehensive collection of germline mutations in nuclear genes that underlie, or are associated with, human inherited disease. By June 2013, the database contained over 141,000 different lesions detected in over 5,700 different genes, with new mutation entries currently accumulating at a rate exceeding 10,000 per annum. HGMD was originally established in 1996 for the scientific study of mutational mechanisms in human genes. However, it has since acquired a much broader utility as a central unified disease-oriented mutation repository utilized by human molecular geneticists, genome scientists, molecular biologists, clinicians and genetic counsellors as well as by those specializing in biopharmaceuticals, bioinformatics and personalized genomics. The public version of HGMD ( https://www.hgmd.cf.ac.uk ) is freely available to registered users from academic institutions/non-profit organizations whilst the subscription version (HGMD Professional) is available to academic, clinical and commercial users under license via BIOBASE GmbH.

Tropical Storm Driven Hydrologic Regimes Support Spartina spartinae Dominated Prairies in Texas - David J. Cooper; Joel I. Wagner (Wetlands, 2013)

MuPIT interactive: webserver for mapping variant positions to annotated, interactive 3D structures - Noushin Niknafs; Dewey Kim; RyangGuk Kim; Mark Diekhans; Michael Ryan; Peter D. Stenson; David N. Cooper; Rachel Karchin (Human Genetics, 2013)

The Creation and Maintenance of Wetland Ecosystems from Irrigation Canal and Reservoir Seepage in a Semi-Arid Landscape - Jeremy P. Sueltenfuss; David J. Cooper; Richard L. Knight; Reagan M. Waskom (Wetlands, 2013)

Where genotype is not predictive of phenotype: towards an understanding of the molecular basis of reduced penetrance in human inherited disease - David N. Cooper; Michael Krawczak; Constantin Polychronakos; Chris Tyler-Smith; Hildegard Kehrer-Sawatzki (Human Genetics, 2013)

Magnitude and time course of changes in maximal oxygen uptake in response to distinct regimens of chronic interval training in sedentary women - Todd A. Astorino; Matthew M. Schubert; Elyse Palumbo; Douglas Stirling; David W. McMillan; Christina Cooper; Jackie Godinez; Donovan Martinez; Rachael Gallant (European Journal of Applied Physiology, 2013)

Paths to selection on life history loci in different natural environments across the native range of A rabidopsis thaliana - Alexandre Fournier‐Level; Amity M. Wilczek; Martha D. Cooper; Judith L. Roe; Jillian Anderson; Deren Eaton; Brook T. Moyers; Renee H. Petipas; Robert N. Schaeffer; Bjorn Pieper; Matthieu Reymond; Maarten Koornneef; et al. (Molecular Ecology, 2013)
Selection on quantitative trait loci ( QTL ) may vary among natural environments due to differences in the genetic architecture of traits, environment‐specific allelic effects or changes in the direction and magnitude of selection on specific traits. To dissect the environmental differences in selection on life history QTL across climatic regions, we grew a panel of interconnected recombinant inbred lines ( RIL s) of Arabidopsis thaliana in four field sites across its native European range. For each environment, we mapped QTL for growth, reproductive timing and development. Several QTL were pleiotropic across environments, three colocalizing with known functional polymorphisms in flowering time genes ( CRY 2 , FRI and MAF 2‐5 ), but major QTL differed across field sites, showing conditional neutrality. We used structural equation models to trace selection paths from QTL to lifetime fitness in each environment. Only three QTL directly affected fruit number, measuring fitness. Most QTL had an indirect effect on fitness through their effect on bolting time or leaf length. Influence of life history traits on fitness differed dramatically across sites, resulting in different patterns of selection on reproductive timing and underlying QTL . In two oceanic field sites with high prereproductive mortality, QTL alleles contributing to early reproduction resulted in greater fruit production, conferring selective advantage, whereas alleles contributing to later reproduction resulted in larger size and higher fitness in a continental site. This demonstrates how environmental variation leads to change in both QTL effect sizes and direction of selection on traits, justifying the persistence of allelic polymorphism at life history QTL across the species range.

On the conversion of tritium units to mass fractions for hydrologic applications - David A. Stonestrom; Brian J. Andraski; Clay A. Cooper; C. Justin Mayers; Robert L. Michel (Isotopes in Environmental and Health Studies, 2013)

Acidity controls on dissolved organic carbon mobility in organic soils - Chris D. Evans; Tim G. Jones; Annette Burden; Nick Ostle; Piotr Zieliński; Mark D. A. Cooper; Mike Peacock; Joanna M. Clark; Filip Oulehle; David Cooper; Chris Freeman (Global Change Biology, 2012)
Dissolved organic carbon ( DOC ) concentrations in surface waters have increased across much of E urope and N orth A merica, with implications for the terrestrial carbon balance, aquatic ecosystem functioning, water treatment costs and human health. Over the past decade, many hypotheses have been put forward to explain this phenomenon, from changing climate and land management to eutrophication and acid deposition. Resolution of this debate has been hindered by a reliance on correlative analyses of time series data, and a lack of robust experimental testing of proposed mechanisms. In a 4 year, four‐site replicated field experiment involving both acidifying and deacidifying treatments, we tested the hypothesis that DOC leaching was previously suppressed by high levels of soil acidity in peat and organo‐mineral soils, and therefore that observed DOC increases a consequence of decreasing soil acidity. We observed a consistent, positive relationship between DOC and acidity change at all sites. Responses were described by similar hyperbolic relationships between standardized changes in DOC and hydrogen ion concentrations at all sites, suggesting potentially general applicability. These relationships explained a substantial proportion of observed changes in peak DOC concentrations in nearby monitoring streams, and application to a UK ‐wide upland soil p H dataset suggests that recovery from acidification alone could have led to soil solution DOC increases in the range 46–126% by habitat type since 1978. Our findings raise the possibility that changing soil acidity may have wider impacts on ecosystem carbon balances. Decreasing sulphur deposition may be accelerating terrestrial carbon loss, and returning surface waters to a natural, high‐ DOC condition.

Methods for reactive oxygen species (ROS) detection in aqueous environments - Justina M. Burns; William J. Cooper; John L. Ferry; D. Whitney King; Brian P. DiMento; Kristopher McNeill; Christopher J. Miller; William L. Miller; Barrie M. Peake; Steven A. Rusak; Andrew L. Rose; T. David Waite (Aquatic Sciences, 2012)

Challenges with Developing In Vitro Dissolution Tests for Orally Inhaled Products (OIPs) - Trevor Riley; David Christopher; Jan Arp; Andrea Casazza; Agnes Colombani; Andrew Cooper; Monisha Dey; Janet Maas; Jolyon Mitchell; Maria Reiners; Nastaran Sigari; Terrence Tougas; et al. (AAPS PharmSciTech, 2012)

Application of recurrence quantification analysis to automatically estimate infant sleep states using a single channel of respiratory data - Philip I. Terrill; Stephen J. Wilson; Sadasivam Suresh; David M. Cooper; Carolyn Dakin (Medical & Biological Engineering & Computing, 2012)

Habitat connectivity, more than species’ biology, influences genetic differentiation in a habitat specialist, the short-eared rock-wallaby (Petrogale brachyotis) - Sally Potter; Mark D. B. Eldridge; Steven J. B. Cooper; Justyna Z. Paplinska; David A. Taggart (Conservation Genetics, 2012)

Intermediate fragmentation per se provides stable predator‐prey metapopulation dynamics - Jennifer K. Cooper; Jiqiu Li; David J. S. Montagnes (Ecology Letters, 2012)
The extent to which a landscape is fragmented affects persistence of predator‐prey dynamics. Increasing fragmentation concomitantly imposes conditions that stabilise and destabilise metapopulations. For the first time, we explicitly assessed the hypothesis that intermediate levels provide optimal conditions for stability. We examine four structural changes arising from increased fragmentation: increased fragment number; decreased fragment size; increased connectedness (corridors scaled to fragment); increased fragment heterogeneity (based on connectedness). Using the model predator‐prey system ( Didinium‐Paramecium ) we support our hypothesis, by examining replicated metapopulations dynamics at five fragmentation levels. Although both species became extinct without fragmentation, prey survived at low and high levels, and both survived at intermediate levels. By examining time to extinction, maximum abundances, and population asynchrony we conclude that fragmentation produces structural heterogeneity (independent of environmental heterogeneity), which influences stability. Our analysis suggests why some theoretical, field and microcosm studies present conflicting views of fragmentation effects on population persistence.

Multiple biogeographical barriers identified across the monsoon tropics of northern Australia: phylogeographic analysis of the brachyotis group of rock‐wallabies - SALLY POTTER; MARK D.B. ELDRIDGE; DAVID A. TAGGART; STEVEN J.B. COOPER (Molecular Ecology, 2012)
The monsoon tropics of northern Australia are a globally significant biodiversity hotspot, but its phylogeography is poorly known. A major challenge for this region is to understand the biogeographical processes that have shaped the distribution and diversity of taxa, without detailed knowledge of past climatic and environmental fluctuations. Although molecular data have great potential to address these questions, only a few species have been examined phylogeographically. Here, we use the widely distributed and abundant short‐eared rock‐wallaby ( Petrogale brachyotis ; n = 101), together with the sympatric monjon ( P. burbidgei ; n = 11) and nabarlek ( P. concinna ; n = 1), to assess historical evolutionary and biogeographical processes in northern Australia. We sequenced ∼1000 bp of mitochondrial DNA (control region, ND2 ) and ∼3000 bp of nDNA ( BRCA1 , ω‐globin and two anonymous loci) to investigate phylogeographic structuring and delineate the time‐scale of diversification within the region. Our results indicate multiple barriers between the Top End (Northern Territory) and Kimberley (Western Australia), which have caused divergence throughout the Plio‐Pleistocene. Eight geographically discrete and genetically distinct lineages within the brachyotis group were identified, five of which are separated by major river valleys (Ord, Victoria, Daly), arid lowlands and discontinuous sandstone ranges. It is likely that these barriers have similarly influenced genetic structure in other monsoonal biota.

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

Chemical and physical factors associated with yellow perch abundance in Great Lakes coastal wetlands: patterns within and among wetland types - Aaron D. Parker; Matthew J. Cooper; Carl R. Ruetz; David P. Coulter; Donald G. Uzarski (Wetlands Ecology and Management, 2012)

Structural changes in the hippocampus and amygdala at first episode of psychosis - David R. Watson; Feng Bai; Suzanne L. Barrett; Aidan Turkington; Teresa M. Rushe; Ciaran C. Mulholland; Stephen J. Cooper (Brain Imaging and Behavior, 2012)

Levels of novel hybridization in the saltcedar invasion compared over seven decades - John F. Gaskin; Adam S. Birken; David J. Cooper (Biological Invasions, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Challenges and Opportunities in Implementing the FDA Default Parametric Tolerance Interval Two One-Sided Test for Delivered Dose Uniformity of Orally Inhaled Products - Greg Larner; Andrew Cooper; Svetlana Lyapustina; Stefan Leiner; David Christopher; Helen Strickland; Michael Golden; Hans-Joachim Delzeit; Emil M. Friedman (AAPS PharmSciTech, 2011)

Ecosystem response to removal of exotic riparian shrubs and a transition to upland vegetation - Lindsay V. Reynolds; David J. Cooper (Plant Ecology, 2011)

Synthesis and characterization of an unsymmetrical cobalt(III) active site analogue of nitrile hydratase - Jennifer K. Angelosante; Lauren M. Schopp; Breia J. Lewis; Amber D. Vitalo; Dustin T. Titus; Rebecca A. Swanson; April N. Stanley; Brendan P. Abolins; Michelle J. Frome; Lisa E. Cooper; David L. Tierney; Curtis Moore; et al. (JBIC Journal of Biological Inorganic Chemistry, 2011)

Lionizing lyonization 50 years on - David N. Cooper (Human Genetics, 2011)

Delineating the Hemostaseome as an aid to individualize the analysis of the hereditary basis of thrombotic and bleeding disorders - Kim Fechtel; Marika L. Osterbur; Hildegard Kehrer-Sawatzki; Peter D. Stenson; David N. Cooper (Human Genetics, 2011)

Reply to comment on “A framework for understanding the hydroecology of impacted wet meadows in the Sierra Nevada and Cascade Ranges, California, USA”: paper published in Hydrogeology Journal (2009) 17:229–246, by Steven P. Loheide II, Richard S. Deitchman, David J. Cooper, Evan C. Wolf, Christopher T. Hammersmark, Jessica D. Lundquist - Steven P. Loheide; Richard S. Deitchman; David J. Cooper; Evan C. Wolf; Christopher T. Hammersmark; Jessica D. Lundquist (Hydrogeology Journal, 2010)

Interannual Variation in Photosynthetically Significant Optical Properties and Water Quality in a Coastal Blackwater River Plume - Michael J. Durako; Piotr Kowalczuk; Michael A. Mallin; William J. Cooper; Jason J. Souza; David H. Wells (Estuaries and Coasts, 2010)

Mountain Fen Distribution, Types and Restoration Priorities, San Juan Mountains, Colorado, USA - Rod A. Chimner; Joanna M. Lemly; David J. Cooper (Wetlands, 2010)

Morphological and architectural development of root systems in sorghum and maize - Vijaya Singh; Erik J. van Oosterom; David R. Jordan; Carlos D. Messina; Mark Cooper; Graeme L. Hammer (Plant and Soil, 2010)

Synchronized changes to relative neuron populations in postnatal human neocortical development - David L. Cooper; James E. Gentle; Ernest Barreto; James L. Olds (Cognitive Neurodynamics, 2010)

What Conservation Biologists Can Do to Counter Trap‐Neuter‐Return: Response to Longcore et al. - CHRISTOPHER A. LEPCZYK; NICO DAUPHINÉ; DAVID M. BIRD; SHEILA CONANT; ROBERT J. COOPER; DAVID C. DUFFY; PAMELA JO HATLEY; PETER P. MARRA; ELIZABETH STONE; STANLEY A. TEMPLE (Conservation Biology, 2010)

Sedimentation of acantharian cysts in the Iceland Basin: Strontium as a ballast for deep ocean particle flux, and implications for acantharian reproductive strategies - Patrick Martin; John T. Allen; Matthew J. Cooper; David G. Johns; Richard S. Lampitt; Richard Sanders; Damon A. H. Teagle (Limnology and Oceanography, 2010)
Acantharian cysts were discovered in sediment trap samples from spring 2007 at 2000 m in the Iceland Basin. Although these single‐celled organisms contribute to particulate organic matter flux in the upper mesopelagic, their contribution to bathypelagic particle flux has previously been found negligible. Four time‐series sediment traps were deployed and all collected acantharian cysts, which are reproductive structures. Across all traps, cysts contributed on average 3–22%, and 4–24% of particulate organic carbon and nitrogen (POC and PON) flux, respectively, during three separate collection intervals (the maximum contribution in any one trap was 48% for POC and 59% for PON). Strontium (Sr) flux during these 6 weeks reached 3 mg m −2 d −1 . The acantharian celestite (SrSO 4 ) skeleton clearly does not always dissolve in the mesopelagic as often thought, and their cysts can contribute significantly to particle flux at bathypelagic depths during specific flux events. Their large size (~ 1 mm) and mineral ballast result in a sinking rate of ~ 500 m d −1 ; hence, they reach the bathypelagic before dissolving. Our findings are consistent with a vertical profile of salinity‐normalized Sr concentration in the Iceland Basin, which shows a maximum at 1700 m. Profiles of salinity‐normalized Sr concentration in the subarctic Pacific reach maxima at ≤ 1500 m, suggesting that Acantharia might contribute to the bathypelagic particle flux there as well. We hypothesize that Acantharia at high latitudes use rapid, deep sedimentation of reproductive cysts during phytoplankton blooms so that juveniles can exploit the large quantity of organic matter that sinks rapidly to the deep sea following a bloom.

Decomposition of plankton‐derived dissolved organic matter in permeable coastal sediments - Lindsay Chipman; David Podgorski; Stefan Green; Joel Kostka; William Cooper; Markus Huettel (Limnology and Oceanography, 2010)
We tested the hypothesis that dissolved organic carbon (DOC) is degraded when filtered through permeable shelf sediments. In a laboratory flume experiment the concave shape of DOC profiles observed in the upper 10 cm of Gulf of Mexico sublittoral sands was reproduced by the combination of DOC filtration and production in the sediment surface layer and mineralization and adsorption in the subsurface layer. Six percent to 14% of 13 C‐labeled, highly degradable DOC was mineralized during filtration through 5.8‐cm‐long sand‐filled column reactors, up to nine times more than in dark, water‐filled column reactors. Filtration through 50‐cm‐long sand columns removed all highly degradable DOC pumped through the sediment, translating to fluxes of up to 379 mmol DOC m −2 d −1 , corresponding to DOC removal from an approximately 1‐m‐deep water layer each day. Bacterial incorporation of 13 C identified a diverse group of sedimentary aerobic and anaerobic microbes processing DO 13 C filtered through sand columns, dominated by Gammaproteobacteria , Deltaproteobacteria , Firmicutes , Bacteroidetes , and Planctomycetes . Excitation‐emission matrix spectroscopy analysis of chromophoric dissolved organic matter contained in diatom‐derived DOC indicated that microbes preferentially removed components around the fluorescence peak of tryptophan or protein‐like substances, which may have the highest nutrient value. Mass spectra analysis revealed that filtration through sand also removes a broad spectrum of substances from less degradable humic and fulvic acid‐like DOC and produces new DOC components. The flushed sand layer between the water column and deeper anoxic sediment layers acts as an effective DOC filter, with subsurface horizontal pore‐water flows promoting decomposition of DOC.

Memory reconsolidation for natural language processing - Kun Tu; David G. Cooper; Hava T. Siegelmann (Cognitive Neurodynamics, 2009)

Sequence and In Silico Characterization of the Tomato Polygalacturonase (PG) Promoter and Terminator Regions - Joann M. Lau; Nigel G. Cooper; David L. Robinson; Schuyler S. Korban (Plant Molecular Biology Reporter, 2009)

Re‐examination of a proposed case of stasipatric speciation: phylogeography of the Australian morabine grasshoppers ( Vandiemenella viatica species group) - TAKESHI KAWAKAMI; ROGER K. BUTLIN; MARK ADAMS; KATHLEEN M. SAINT; DAVID J. PAULL; STEVEN J. B. COOPER (Molecular Ecology, 2009)
Karyotypic differences have been used for delimiting populations or species, although whether these mutations provide strong barriers to gene flow between populations and promote speciation remains contentious. In this study, we assessed whether 11 chromosomal races of Australian morabine grasshoppers ( Vandiemenella viatica species group) represent genetically distinct populations by analyses of cytological and allozyme (35 loci) data and DNA sequences of the elongation factor‐1 alpha ( EF ‐1α), anonymous Mvia11 , and mitochondrial cytochrome c oxidase subunit I ( COI ) loci. While the Vandiemenella chromosomal taxa generally represent genetically distinct units, a substantial portion of the total genetic variation in our samples was not explained by the chromosomal variation. Mantel tests indicated that Vandiemenella populations were spatially structured and have maintained gene flow at a local scale within each of the taxa. The group was subdivided into 13 genetic clusters; four chromosomal taxa comprised single exclusive clusters, while others comprised more than one cluster or clusters shared with other taxa. Boundaries of these cryptic population subdivisions correspond with several biogeographical barriers, such as straits, gulfs, the Murray River, and an ancient mega‐lake, Lake Bungunnia. The viatica species group was previously proposed to have diversified without major geographical separation based on the stasipatric speciation model; however, the present study suggests the involvement of allopatric fragmentation. Given extensive nonmonophyly of chromosomal taxa and incomplete barriers to gene flow among taxa, all Vandiemenella chromosomal taxa and genetically distinct populations within chromosomal taxa, except Vandiemenella pichirichi , should be regarded as populations of one species: Vandiemenella viatica .

Cruciform-forming inverted repeats appear to have mediated many of the microinversions that distinguish the human and chimpanzee genomes - Jessica Kolb; Nadia A. Chuzhanova; Josef Högel; Karen M. Vasquez; David N. Cooper; Albino Bacolla; Hildegard Kehrer-Sawatzki (Chromosome Research, 2009)

Huntington F. Willard and Geoffrey S. Ginsburg (eds): Genomic and personalized medicine - David N. Cooper (Human Genetics, 2009)

STREGA: a ‘How-To’ guide for reporting genetic associations - Thomas J. Hudson; David N. Cooper (Human Genetics, 2009)

Air pollution and mutations in the germline: are humans at risk? - Christopher M. Somers; David N. Cooper (Human Genetics, 2009)

The insect caspases - Dawn M. Cooper; David J. Granville; Carl Lowenberger (Apoptosis, 2009)

A framework for understanding the hydroecology of impacted wet meadows in the Sierra Nevada and Cascade Ranges, California, USA - Steven P. Loheide; Richard S. Deitchman; David J. Cooper; Evan C. Wolf; Christopher T. Hammersmark; Jessica D. Lundquist (Hydrogeology Journal, 2009)

Enhanced Resistance to Control Potato Tuberworm by Combining Engineered Resistance, Avidin, and Natural Resistance Derived from, Solanum Chacoense - Susannah G. Cooper; David S. Douches; Kelly Zarka; Edward J. Grafius (American Journal of Potato Research, 2009)

Distortions of auditory space during rapid head turns - Joel Cooper; Simon Carlile; David Alais (Experimental Brain Research, 2008)

Landscape based identification of human disturbance gradients and reference conditions for Michigan streams - Lizhu Wang; Travis Brenden; Paul Seelbach; Arthur Cooper; David Allan; Richard Clarck; Michael Wiley (Environmental Monitoring and Assessment, 2008)

Landscape Based Identification of Human Disturbance Gradients and Reference Conditions for Michigan Streams - Lizhu Wang; Travis Brenden; Paul Seelbach; Arthur Cooper; David Allan; Richard Clark; Michael Wiley (Environmental Monitoring and Assessment, 2008)

Molecular mechanisms of chromosomal rearrangement during primate evolution - Hildegard Kehrer-Sawatzki; David N. Cooper (Chromosome Research, 2008)

Evaluation of laboratory-based measures of soil mineral nitrogen and potentially mineralizable nitrogen as predictors of field-based indices of soil nitrogen supply in potato production - Mehdi Sharifi; Bernie J. Zebarth; David L. Burton; Cynthia A. Grant; Gregory A. Porter; Julia M. Cooper; Yves Leclerc; Gilles Moreau; Walter J. Arsenault (Plant and Soil, 2007)

Elk browsing increases aboveground growth of water-stressed willows by modifying plant architecture - Danielle B. Johnston; David J. Cooper; N. Thompson Hobbs (Oecologia, 2007)

Characterization of polychlorinated alkane mixtures—a Monte Carlo modeling approach - Soren R. Jensen; Wayne A. Brown; Ester Heath; David G. Cooper (Biodegradation, 2007)

Editorial - David N. Cooper; Thomas J. Hudson (Human Genetics, 2007)

Dams, Floodplain Land Use, and Riparian Forest Conservation in the Semiarid Upper Colorado River Basin, USA - Douglas C. Andersen; David J. Cooper; Krista Northcott (Environmental Management, 2007)

Determining net dissolved organic carbon production in the hydrographically complex western Arctic Ocean - Jeremy T. Mathis; Dennis A. Hansell; David Kadko; Nicholas R. Bates; Lee W. Cooper (Limnology and Oceanography, 2007)
Each spring and summer, the Chukchi Sea in the western Arctic Ocean experiences a short but intense phytoplankton bloom that is controlled by sea ice cover, nutrient availability, and river runoff. During the bloom, dissolved inorganic carbon (DIC) concentrations are drawn down in the mixed layer (shelf, ~Δ100 µmol kg −1 ; shelf‐break, ~Δ50 µmol kg −1 ; basin, −1 ) and converted to particulate organic carbon (POC) and dissolved organic carbon (DOC). We use δ 18 O and salinity to estimate DOC inputs by river and sea ice melt, allowing the marine portion of the DOC pool to be compared between seasons and to facilitate estimates of net DOC production in the region. We estimate that ~10% of the DIC consumed during net community production is converted to DOC. The remaining carbon deficit (90% of DIC drawdown) is most likely exported from the mixed layer as POC. In 2002 a carbon (C) mass balance was developed for the Chukchi Sea that showed that rates of vertical export were highest over the Chukchi Shelf near Point Barrow (64 mmol C m − d −1 ), but more commonly ranged from 10 to 35 mmol C m − d −1 over the remainder of the shelf. At the shelf‐break and in the Canada Basin export production was − d −1 . DOC plays a relatively small role as a carbon sink in the system, but quantifying its contributions provides more robust estimates of export production in the Arctic.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Assessment of Stream Ecosystem Function and Sensitivity in the Bighorn National Forest, Wyoming - Ellen Wohl; David Cooper; LeRoy Poff; Frank Rahel; Dennis Staley; David Winters (Environmental Management, 2007)

Effects of river regulation on riparian box elder (Acer Negundo) forests in Canyons of the upper Colorado River Basin, USA - John M. DeWine; David J. Cooper (Wetlands, 2007)

The use of hydrologic and Ecological indicators for the restoration of drainage ditches and water diversions in a Mountain Fen, Cascade Range, California - Lindsay Patterson; David J. Cooper (Wetlands, 2007)

Effect of surfactants on plasticizer biodegradation by Bacillus subtilis ATCC 6633 - Adam R. Grochowalski; David G. Cooper; Jim A. Nicell (Biodegradation, 2007)

Fish swimming speed variability at constant flow: Galaxias maculatus - David R. Plew; Vladimir I. Nikora; Scott T. Larned; Julian R. E. Sykes; Glenn G. Cooper (New Zealand Journal of Marine and Freshwater Research, 2007)
Digital videography was used to study the swimming performance of the adult fish Galaxias maculatus in a flume at fixed flows. Instantaneous fish swimming velocities varied about the mean flume velocity and these variations in swimming speed were found to increase as velocity in the flume increased. Standard deviations in swimming velocity measured in the longitudinal direction increased from SD 0.183 m s –1 at U 0 = 0.40 m s –1 , SD 0.191 at U 0 = 0.48 m s –1 to SD 0.237 m s –1 at U 0 = 0.60 m s –1 . Increases in standard deviations were also seen in cross‐stream and vertical swimming velocities. Similarly, variability in acceleration increased as flume velocity was increased with SD 1.850 m s –2 at U 0 = 0.40 m s ‐1 , SD 2.492 m s –2 at U 0 = 0.48 m s –1 , and SD 3.125 m s –2 at U 0 = 0.60 m s –1 recorded for the longitudinal acceleration component. Maximum swimming velocities of 2.05 m s –1 and accelerations of 25.4 m s –2 were recorded.

Structural divergence between the human and chimpanzee genomes - Hildegard Kehrer-Sawatzki; David N. Cooper (Human Genetics, 2007)

Common variants in the TCF7L2 gene and predisposition to type 2 diabetes in UK European Whites, Indian Asians and Afro-Caribbean men and women - Steve E. Humphries; David Gable; Jackie A. Cooper; Helen Ireland; Jeffrey W. Stephens; Steven J. Hurel; Ka Wah Li; Jutta Palmen; Michelle A. Miller; Francesco P. Cappuccio; Robert Elkeles; Ian Godsland; et al. (Journal of Molecular Medicine, 2006)

A systematic analysis of disease-associated variants in the 3′ regulatory regions of human protein-coding genes II: the importance of mRNA secondary structure in assessing the functionality of 3′ UTR variants - Jian-Min Chen; Claude Férec; David N. Cooper (Human Genetics, 2006)

Complex patterns of copy number variation at sites of segmental duplications: an important category of structural variation in the human genome - Violaine Goidts; David N. Cooper; Lluis Armengol; Werner Schempp; Jeffrey Conroy; Xavier Estivill; Norma Nowak; Horst Hameister; Hildegard Kehrer-Sawatzki (Human Genetics, 2006)

Characterization of the human lineage-specific pericentric inversion that distinguishes human chromosome 1 from the homologous chromosomes of the great apes - Justyna M. Szamalek; Violaine Goidts; David N. Cooper; Horst Hameister; Hildegard Kehrer-Sawatzki (Human Genetics, 2006)

A systematic analysis of disease-associated variants in the 3′ regulatory regions of human protein-coding genes I: general principles and overview - Jian-Min Chen; Claude Férec; David N. Cooper (Human Genetics, 2006)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Identification of large-scale human-specific copy number differences by inter-species array comparative genomic hybridization - Violaine Goidts; Lluis Armengol; Werner Schempp; Jeffrey Conroy; Norma Nowak; Stefan Müller; David N. Cooper; Xavier Estivill; Wolfgang Enard; Justyna M. Szamalek; Horst Hameister; Hildegard Kehrer-Sawatzki (Human Genetics, 2006)

Polymorphic micro-inversions contribute to the genomic variability of humans and chimpanzees - Justyna M. Szamalek; David N. Cooper; Werner Schempp; Peter Minich; Matthias Kohn; Josef Hoegel; Violaine Goidts; Horst Hameister; Hildegard Kehrer-Sawatzki (Human Genetics, 2006)

Searching for signals of evolutionary selection in 168 genes related to immune function - Emily C. Walsh; Pardis Sabeti; Holli B. Hutcheson; Ben Fry; Stephen F. Schaffner; Paul I. W. de Bakker; Patrick Varilly; Alejandro A. Palma; Jessica Roy; Richard Cooper; Cheryl Winkler; Yi Zeng; et al. (Human Genetics, 2006)

Facilitating Physiologic Self-Regeneration: A Step Beyond Islet Cell Replacement - Pleunie P. M. Rood; Rita Bottino; A. N. Balamurugan; Yong Fan; David K. C. Cooper; Massimo Trucco (Pharmaceutical Research, 2006)

A systematic analysis of LINE-1 endonuclease-dependent retrotranspositional events causing human genetic disease - Jian-Min Chen; Peter D. Stenson; David N. Cooper; Claude Férec (Human Genetics, 2005)

Molecular characterisation of the pericentric inversion that distinguishes human chromosome 5 from the homologous chimpanzee chromosome - Justyna M. Szamalek; Violaine Goidts; Nadia Chuzhanova; Horst Hameister; David N. Cooper; Hildegard Kehrer-Sawatzki (Human Genetics, 2005)

Mechanisms of Riparian Cottonwood Decline Along Regulated Rivers - Christopher A. Williams; David J. Cooper (Ecosystems, 2005)

The α-Globin Gene Family of an Australian Marsupial, Macropus eugenii: The Long Evolutionary History of the θ-Globin Gene and Its Functional Status in Mammals - Steven J.B. Cooper; David Wheeler; Rory M. Hope; Gaynor Dolman; Kathleen M. Saint; Andrew A. Gooley; Robert A.B. Holland (Journal of Molecular Evolution, 2005)

Establishing a Context for River Rehabilitation, North Fork Gunnison River, Colorado - Christopher Jaquette; Ellen Wohl; David Cooper (Environmental Management, 2005)

Cortisol response to diazepam: its relationship to age, dose, duration of treatment, and presence of generalized anxiety disorder - Nunzio Pomara; Lisa M Willoughby; John J Sidtis; Thomas B Cooper; David J Greenblatt (Psychopharmacology, 2005)

Constraints on willow seedling survival in a Rocky Mountain Montane floodplain - Edward A. Gage; David J. Cooper (Wetlands, 2004)

Analysis of Sediment Retention in Western Riverine Wetlands: The Yampa River Watershed, Colorado, USA - Christopher D. Arp; David J. Cooper (Environmental Management, 2004)

Linkage of the β-Like ω-Globin Gene to α-Like Globin Genes in an Australian Marsupial Supports the Chromosome Duplication Model for Separation of Globin Gene Clusters - David Wheeler; Rory M. Hope; Steven J. B. Cooper; Andrew A. Gooley; Robert A. B. Holland (Journal of Molecular Evolution, 2004)

Using stable oxygen isotopes to quantify the water source used for transpiration by native shrubs in the San Luis Valley, Colorado U.S.A. - Rodney A. Chimner; David J. Cooper (Plant and Soil, 2004)

The sensitivity of medicare data for identifying incident cases of invasive melanoma (United States) - David A. Barzilai; Siran M. Koroukian; Duncan Neuhauser; Kevin D. Cooper; Alfred A. Rimm; Gregory S. Cooper (Cancer Causes & Control, 2004)

Human genetic disease caused by de novo mitochondrial-nuclear DNA transfer - Clesson Turner; Christina Killoran; Nick S. T. Thomas; Marjorie Rosenberg; Nadia A. Chuzhanova; Jennifer Johnston; Yelena Kemel; David N. Cooper; Leslie G. Biesecker (Human Genetics, 2003)

Physiological and Morphological Response Patterns of Populus deltoides to Alluvial Groundwater Pumping - DAVID J. COOPER; DONALD R. D'AMICO; MICHAEL L. SCOTT (Environmental Management, 2003)

Managing Troubled Data: Coastal Data Partnerships Smooth Data Integration - Stephen S. Hale; Anne Hale Miglarese; M. Patricia Bradley; Thomas J. Belton; Larry D. Cooper; Michael T. Frame; Christopher A. Friel; Linda M. Harwell; Robert E. King; William K. Michener; David T. Nicolson; Bruce G. Peterjohn (Environmental Monitoring and Assessment, 2003)

A new mouse mutant, skijumper - Majid Hafezparast; Simon Ball; Sharon J. Nicholson; Abi Witherden; Demet Arac; Neil Broadway; David Saggerson; Edwin Cooper; Mahmoud Naase; Stephen Gokhale; Patti Quant; Carol Lascelles; et al. (Mammalian Genome, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

Modeling carbon accumulation in Rocky Mountain fens - Rodney A. Chimner; David J. Cooper; William J. Parton (Wetlands, 2002)

A candidate gene for congenital bilateral isolated ptosis identified by molecular analysis of a de novo balanced translocation - Tristan F. McMullan; John A. Crolla; Simon G. Gregory; Nigel P. Carter; Rachel A. Cooper; Gareth R. Howell; David O. Robinson (Human Genetics, 2002)

Wiley encyclopedia of molecular medicine - David N. Cooper (Human Genetics, 2002)

Proposed guidelines for papers describing DNA polymorphism-disease associations - David N. Cooper; Robert L. Nussbaum; Michael Krawczak (Human Genetics, 2002)

The clinical grading of Raynaud's phenomenon and vibration-induced white finger: relationship between finger blanching and difficulties in using the upper limb - Keith T. Palmer; Michael J. Griffin; Holly Syddall; Cyrus Cooper; David Coggon (International Archives of Occupational and Environmental Health, 2002)

Evaluation of denaturing high performance liquid chromatography (DHPLC) for the mutational analysis of the neurofibromatosis type 1 ( NF1 ) gene - Song Han; David Cooper; Meena Upadhyaya (Human Genetics, 2001)

Comparison of two equivalency factor approaches with simplified risk assessment for lcia of toxicity impact potential - Duane A. Tolle; David J. Hesse; G. Bradley Chadwell; Joyce S. Cooper; David P. Evers (The International Journal of Life Cycle Assessment, 2001)

Human type I hair keratin pseudogene ? hHaA has functional orthologs in the chimpanzee and gorilla: evidence for recent inactivation of the human gene after the Pan-Homo divergence - Hermelita Winter; Lutz Langbein; Michael Krawczak; David Cooper; Luis Jave-Suarez; Michael Rogers; Silke Praetzel; Peter Heidt; Jrgen Schweizer (Human Genetics, 2001)

SUPPRESSION OF ANTIGEN-SPECIFIC LYMPHOCYTE ACTIVATION IN MODELED MICROGRAVITY - DAVID COOPER; MICHAEL W. PRIDE; ERIC L. BROWN; DIANA RISIN; NEAL R. PELLIS (In Vitro Cellular & Developmental Biology - Animal, 2001)

Changes in primary DNA sequence complexity influence the phenotypic consequences of mutations in human gene regulatory regions - Michael Krawczak; Nadia Chuzhanova; Peter Stenson; Bent Johansen; Edward Ball; David Cooper (Human Genetics, 2000)

Hypermethylation of the neurofibromatosis type 1 (NF1) gene promoter is not a common event in the inactivation of the NF1 gene in NF1-specific tumours - Martin P. Horan; David N. Cooper; Meena Upadhyaya (Human Genetics, 2000)

Molecular genetic analysis of severe protein C deficiency - David S. Millar; Bent Johansen; Erik Berntorp; Adrian Minford; Paula Bolton-Maggs; Richard Wensley; Vijay Kakkar; Sam Schulman; Argimiro Torres; Norma Bosch; David N. Cooper (Human Genetics, 2000)

Molecular genetic analysis of severe protein C deficiency - David S. Millar; Bent Johansen; Erik Berntorp; Adrian Minford; Paula Bolton-Maggs; Richard Wensley; Vijay Kakkar; Sam Schulman; Argimiro Torres; Norma Bosch; David N. Cooper (Human Genetics, 2000)

Temporal distribution of waterfowl in eastern South Dakota: Implications for aerial surveys - David E. Naugle; Rex R. Johnson; Thomas R. Cooper; Matthew M. Holland; Kenneth F. Higgins (Wetlands, 2000)

The effects of acid rock drainage onCarex aquatilis leaf litter decomposition in rocky Mountain fens - Christopher D. Arp; David J. Cooper; John D. Stednick (Wetlands, 1999)

Variation of site-specific methylation patterns in the factor VIII ( F8C ) gene in human sperm DNA - David S. Millar; Michael Krawczak; D. N. Cooper (Human Genetics, 1998)

Hydrologic restoration of a fen in Rocky Mountain National Park, Colorado, USA - David J. Cooper; Lee H. MacDonald; Shaunda K. Wenger; Scott W. Woods (Wetlands, 1998)

The molecular genetics of growth hormone deficiency - A. M. Procter; John A. Phillips III.; David N. Cooper (Human Genetics, 1998)

A Unified Method for Calculating the Center of Pressure during Wheelchair Propulsion - David P. VanSickle; Rory A. Cooper; Michael L. Boninger; Rick N. Robertson; Sean D. Shimada (Annals of Biomedical Engineering, 1998)

Mapping the multiple self-healing squamous epithelioma (MSSE) gene and investigation of xeroderma pigmentosum group A (XPA) and PATCHED (PTCH) as candidate genes - F. M. Richards; David R. Goudie; Wendy N. Cooper; Quitz Jene; Inês Barroso; Carol Wicking; Brandon J. Wainwright; M. A. Ferguson-Smith (Human Genetics, 1997)

Implications of ozone depletion for surface-water photochemistry: Sensitivity of clear lakes - Norman M. Scully; Warwick F. Vincent; David R. S. Lean; William J. Cooper (Aquatic Sciences, 1997)

Changes in gravity inhibit lymphocyte locomotion through type I collagen - Neal R. Pellis; Thomas J. Goodwin; Diana Risin; Bradley W. McIntyre; Roland P. Pizzini; David Cooper; Tacey L. Baker; Glenn F. Spaulding (In Vitro Cellular & Developmental Biology - Animal, 1997)

Implications of ozone depletion for surface-water photochemistry: Sensitivity of clear lakes - Norman M. Scully; Warwick F. Vincent; David R. S. Lean; William J. Cooper (Aquatic Sciences, 1997)

Catabolism of 3-hydroxybenzoate by the gentisate pathway in Klebsiella pneumoniae M5a1 - David C. N. Jones; Ronald A. Cooper (Archives of Microbiology, 1990)

Uptake, elimination, and metabolism of14C-picric acid and14C-picramic acid in the American oyster (Crassostrea virginica) - Dennis T. Burton; Keith R. Cooper; William L. Goodfellow; David H. Rosenblatt (Archives of Environmental Contamination and Toxicology, 1984)

The delayed neuropathic effects of nerve agents and some other organophosphorus compounds - James J. Gordon; Robert H. Inns; Martin K. Johnson; Levence Leadbeater; Michael P. Maidment; David G. Upshall; Graham H. Cooper; Robert L. Rickard (Archives of Toxicology, 1983)